A bibliometrics review of non-CO2 greenhouse gas reduction strategies - Yi-Ming Wei; Si-Yu Liu; Li-Jing Liu; Lan-Cui Liu; Qiao-Mei Liang; Xiao-Chen Yuan; Hong-Dian Jiang; Pallav Purohit; Felix Creutzig; Hua Liao; Biying Yu (Energy and Climate Change, 2026)

Structurally diverse sesquiterpenoids from Curcuma longa and their anti-inflammatory activities - Guang-Han Li; Chun-Mei Qiu; Guang-Xu Wu; Miao Dai; Rui Feng; Hai-Guo Su; Liang Xiong (Phytochemistry, 2026)

Contribution of the slab fluids- melts to petrogenesis of adakitic rocks related to gold mineralization: Mo isotopic constraints - Shu-wen Li; Wen-liang Xu; Qun Yang; Yun-sheng Ren; Wu-shuang Zhang; Bin Wang; Kan Gao; Si-tong Chen; Yao-heng Fang; Hao-zhe Li; Tian-ci Liu; Xuan-mei Xue; et al. (Lithos, 2026)

Scalable cancer cell-derived liposome capable of homologous tumor-homing to encapsulate near-infrared light-responsive drug delivery nanocomposites for enhanced combination therapy - Fang-Yi Hsu; Wen-Jyun Wang; Li-Ting Yang; Yi-Zi Chen; Ting-Chi Lo; Jia-Sin Chen; Wei-Lun Huang; Yen-Liang Li; Hidenobu Takahashi; Wen-Chun Hung; Chi-Wen Luo; Shu-Yi Lin; et al. (Chemical Engineering Journal, 2026)

Multi-environmental biodegradation of a cellulose-based/polylactic acid non-leaching antibacterial composite membrane - Xianpei Xu; Hongbo Wang; Junming Liang; Youbo Di; Mei Liu; Fu Li; Pengfei Fei (Biomass and Bioenergy, 2026)

Nori and kelp intake attenuates antibiotic-induced gut dysbiosis and resistome expansion - Shilin Hu; Jin-Feng Xi; Tian Liang; Jia-Yang Xu; Ying-Xin Xue; Xin-Wei Yu; Jing-Jing Peng; Hong-Bo Li; Xi-Mei Xue (Journal of Environmental Sciences, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

Electrochemical strategies for efficient PFAS removal from water: Mechanisms, performance, and sustainability perspectives - Kaini Peng; Jiale Lin; Mei Chen; Junjian Zheng; Yang Li; Liang Tang (Journal of Hazardous Materials, 2026)

Calcination-modulated Cu redistribution in CuZr catalysts governs downstream ethylene glycol hydrogenolysis in dimethyl oxalate-to-ethanol conversion - Bolun Mei; Yueru Wang; Zhouxuan Zang; Ouyang Liu; Xu Liang; Guoji Liu; Han Sun; Xingchuan Yang; Li Xu (Chemical Engineering Journal, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Trichodermine A, a new polyketide from the endophytic Trichoderma sp. MH550506.1 associated with Gardenia jasminoides - Yan-Li Zhang; Jie-Zhen Shi; Tong-De Zhao; Han-Wei Ruan; Ju-Cheng Zhang; Jin-Hua Yu; Da-Mei Wang; Li-Feng Wang; Liang Deng; Dong Gan; Zhong-Tao Ding (Phytochemistry Letters, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

Parametrization and improvement of the soil evaporation estimation model: Coupling superposition based on fractional canopy cover and soil moisture - Xuefeng Qiu; Xiaoyang Liang; Hang Wang; Jiandong Wang; Guoli Li; Lei Zhang; Hao Zhang; Dingtian Zhou; Xurong Mei (Journal of Hydrology, 2026)

Biodegradable plastic mulches: Distinct effects on microbial communities but no impact on soil multifunctionality during cabbage production - Rong Liang; Lei Mei; Jina Ding; Li Wang; Mouliang Xiao; Yongfu Li; Xiao Liu; Changlong Shao; David R. Chadwick; Davey Jones; Fan Ding; Can Hu; et al. (Journal of Hazardous Materials, 2026)

Roles of coexisting protein in a coupled capacitive deionizing membrane distillation (CDIMD) system treating fluoride-rich brackish groundwater: An especial focus on the complexation-assisting pattern and adsorption-assisting pattern in scaling control - Zhenghao Ni; Chang Liu; Xueting Li; Liang Zhu; Mei Pan (Journal of Environmental Chemical Engineering, 2026)

Efficacy and Mechanisms of Combined Central-Peripheral Magnetic Stimulation on Prefrontal-Sensorimotor Cortex Connectivity in Post-Stroke Dysphagia after Supratentorial Stroke: A Randomized, Single-Blind, Parallel-Controlled Trial - Zirui Luo; Zhiying Zhu; Yujue Wang; Na Su; Yajing Xue; Wanqi Zhang; Wei Liao; Yaoyao You; Lin Ling; Mei Li; Junjie Liang; Zulin Dou; et al. (Translational Stroke Research, 2026)

Infection risks associated with b/tsDMARDs in rheumatoid arthritis: a systematic review and network meta-analysis - Xue-Mei Zhang; Li Liu; Yi-Dan Yan; Zai-Li Zhang; Ke-Jia Le; Yang-Xi Liu; Xiao-Jun Ni; Liang-Jing Lu; Guo-Hua Zhou; Zhi-Chun Gu; Jia Li; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2026)

Olfactory dysfunction is associated with gait impairment in older adults: evidence for a shared amygdala substrate - Jianwei Wang; Jialin Li; Qiu Xiao; Jincheng Li; Hao Wang; Xiao Liang; Siyu Wu; Yingzhe Wang; Mei Cui; Xingdong Chen; Chen Suo; Yanfeng Jiang (GeroScience, 2026)

Three new diterpenoids from the aerial parts of Callicarpa macrophylla - Liang Gou; Rong-Shuai Li; Jian-Lin Lai; Yan-Mei Ning; Xue-Ting Ji; Xiong Qiu; Chao Peng; Xiao-Li Li; Xing-Jie Zhang; Wei-Lie Xiao (Natural Product Research, 2026)

New ecdysteroids with anticomplementary activity from roots of Leuzea uniflora (L.) holub - Wen-qing Du; Can Liu; Ruo-mei Li; Ning-ning Shi; Yan-nan Ji; Jin-long Qi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

Individual and joint association between per- and polyfluoroalkyl substances and skeletal muscle among 6-9 years old children in China - Xue-Mei Liao; Li-Zi Lin; Wan-Ting He; Yun-Ting Zhang; Si-Hui Guo; Shu-Jun Liang; Zhen Hong; Zhe-Qing Zhang; Guang-Hui Dong; Qin-Zhi Wei (International Journal of Hygiene and Environmental Health, 2026)

Heteronemin suppresses chemoresistant oral squamous cell carcinoma cells through ROS-mediated apoptosis and cuproptosis-associated mitochondrial stress - Chiung-Wei Huang; Fan-Li Lin; Chun-Feng Chang; Hsiao-Hsuan Huang; Wan-Ju Wu; Hui-Min Chang; Mei-Ying Lin; Jue-Liang Hsu; Shih-Ya Hung; Chien Hsing Lee (Apoptosis, 2026)

Phase evolution matters: How Fe(II) reshapes coprecipitate surfaces for enhanced U(VI) adsorption - Chaofei Zhang; Yuan Chen; Huiyang Mei; Weichao Zhang; Beihang Zhang; Wentao Zhang; Ping Li; Zhenying Lv; Jianjun Liang; Qiaohui Fan (Water Research, 2026)

Synthesis, characterization, and antimicrobial properties of 8-Hydroxyquinoline-based group 4 metal complexes for plant pathogen control - Tiankun Zhao; Baoqing Lv; Yinan Ding; Dongyu Mei; Jing Ma; Qi Zhang; Li Zhang; Qipin Qin; Zhongduo Yang; Shanjia Li; Isabel Correia; Hong Liang; et al. (Pesticide Biochemistry and Physiology, 2026)

Formation process of Fe-Mn Co-precipitates and Its implications for U(VI) immobilization: Mechanisms and environmental factors - Zhenying Lv; Huiyang Mei; Beihang Zhang; Weichao Zhang; Ping Li; Chaofei Zhang; Jianjun Liang; Qiaohui Fan (Journal of Environmental Chemical Engineering, 2026)

Potential structure-immunostimulatory activity relationship of Tartary buckwheat sprout pectic polysaccharides: Influences of molecular mass and esterification degree - Bo Li; Lin Zhang; Ding-Tao Wu; Qin Yuan; Shengpeng Wang; Mao-Ling Tan; Mei-Lin Feng; Yi-Chen Hu; Liang Zou; Zi-Peng Wang; Ya-Nan Cao; Jing-Wei Huang (Food Research International, 2026)

The physicochemical and simulated digestive characteristics of yam flours processed by different thermal processing methods - Ya Huang; Mei Deng; Xuchao Jia; Lihong Dong; Fei Huang; Qin Ma; Mingwei Zhang; Shan Liang; Yanxia Chen; Fengjuan Li; Ruifen Zhang (Food Chemistry, 2026)

Corrigendum to “Hellebrigenin induces cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells through inhibition of Akt” [Chemico. Biol. Interact. 219 (2014) 184-194] - Li-Juan Deng; Li-Ping Hu; Qun-Long Peng; Xiao-Lin Yang; Liang-Liang Bai; Anita Yiu; Yong Li; Hai-Yan Tian; Wen-Cai Ye; Dong-Mei Zhang (Chemico-Biological Interactions, 2026)

High-defect sulfonated carbon derived from beet molasses for effectively biodiesel production by esterification of methanol and oleic acid - Tianhong Mei; Wugan Wei; Huabo Li; Qing Fang; Yan Fang; Xiaoqian Ren; Jianliang Zhu; Jinhua Liang (Biomass and Bioenergy, 2026)

Geniposide ameliorates ferroptosis through the ROS/p38 MAPK/NCOA4/GPX4-mediated ferritinophagy in a co-culture system of HMC3 and SH-SY5Y cells - Liang-Jun Wang; Yu-Chin Chang; Li-Mei An; Bin-Nan Wu (NeuroToxicology, 2026)

A critical review on abiotic geologic hydrogen generation: Mechanisms and controls - Qingxia Zheng; Ruibo Wu; Ping Li; Zhe Ding; Wentao Zhang; Huiyang Mei; Weichao Zhang; Jianjun Liang; Qiaohui Fan (Earth-Science Reviews, 2026)

Engineering of Azotobacter chroococcum enables potential replacement of synthetic nitrogen fertilizer and mitigation of nitrogen pollutants release under medium-fertility field conditions - Ping Tian; Jun-Feng Wang; Dao-Yuan Wang; Yu-Dian Xun; Xiao-Hui Shi; Ming-Zhu Chen; Yun-Ying Liang; Mei-Ting Yang; Qu-Sheng Li (Bioresource Technology, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

Trade-off analysis between soil organic carbon and maize yield under no-tillage: implication for sustainable cropland management - Mei Liang; Yinghao Su; Hui Xu; Ruonan Li; Aizhen Liang; Yan Zhang; Chuang Li; Jinfeng Ma; Hua Zheng (Journal of Environmental Management, 2026)

Computational design of a highly active and stable alkaline pectate lyase: Unraveling the molecular mechanisms for superior performance - Mei Zhao; Haoyang Li; Jiaojiao Chen; Xiaohao Zhang; Xiaohong Pan; Lei Sun; Liang Guo; Xianghui Qi (Food Research International, 2026)

The dual role of polysaccharide in scaling control during the capacitive deionizing membrane distillation (CDIMD) purification of high-fluoride brackish groundwater - Chang Liu; Zhenghao Ni; Xueting Li; Jinghong Liu; Jiayun Shen; Liang Zhu; Mei Pan; Wenlan Yang (Desalination, 2026)

Ultrasensitive and label-free detection of piR-54265 biomarker by solution-gated graphene transistors with poly-adenine DNA assembled probe for accurate diagnosis of colorectal cancer - Tingting Yu; Peng Song; Ruixue Wang; Ziwen Chen; Liang Zhao; Ming Wang; Jianying Wang; Tao Mei; Xianbao Wang; Jinhua Li (Chemical Engineering Journal, 2026)

Pirfenidone attenuates urethral stricture after injury by inhibiting Gli2 mediated HAS2 expression in fibroblasts - Li Zhong; Yan Mengyu; Zhang Jiandong; Sun Peiwang; Liang Yujie; Mei Zhijie; Gao Wuyue; Guo Yuanyuan (Journal of Molecular Histology, 2026)

Key leverage spots for water-energy-food nexus governance in China: Elasticity insights from a multi-regional input-output framework - Xiang-Yan Qian; Li-Jing Liu; Qiao-Mei Liang (Sustainable Production and Consumption, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

Oceanic deoxygenation linked to enhanced water column stratification in the eastern Tethys during Cretaceous Oceanic Anoxic Event 2 - Yu Liang; Yong-Xiang Li; Hongxuan Lu; Huanye Wang; Cece Wang; Cheng Quan; Weiguo Liu; Mei-Fu Zhou; Zhonghui Liu (Global and Planetary Change, 2026)

Competition release dominates growth recovery of four subtropical broadleaved tree species following an extreme snow event - Tong-Liang Xu; Rao-Qiong Yang; Zaw Zaw; Shankar Panthi; Xin-Hua Peng; Ju-Mei Zhang; Pei-Li Fu; Ke-Yan Fang; Ze-Xin Fan (Forest Ecology and Management, 2026)

Artemisia argyi essential oil - loaded β-cyclodextrin/whey protein microcapsules: dual antifungal and disease resistance-inducing effects to enhance blueberry shelf life - Yue-yan Chen; Ning-ying Zhu; Wei Gao; Yu Wang; Mei-qing Li; Dong-liang Wang; Xue-ling Gao; Jin Liang; Hai-wei Zhang (Food Chemistry, 2026)

Quality enhancement of frozen dough steamed bread by Sanxan: A study on multi-stage regulation of gluten-starch matrix - Haojia Zhu; Heqiao Qian; Jie Li; Hanzhang Hao; Ying Huang; Shenying Zhang; Yingxue Che; Mei Liu; Ying Liang; Xueling Zheng; Chong Liu; Limin Li (Food Hydrocolloids, 2026)

Real-time visualization of Nocardia seriolae proliferation and macrophage migration in the Northern snakehead (Channa argus) - Jian Teng; Jian-Ru Liu; Yi-Xiang Zhai; Sheng-Liang Cao; Zhen-Shu Si; Qing-Teng Ren; Xiang-Shan Ji; Mei-Hua Lu; Yu-Bao Li; Yan Zhao (Aquaculture, 2026)

Mechanistic investigations into cytochrome c-U(VI) adsorption-reduction on ferrihydrite: Implications for subsurface microbial U redox under anaerobic conditions - Jiayu Song; Huiyang Mei; Xiangxian Ma; Ghufran Uddin; Jianjun Liang; Ping Li; Weichao Zhang; Qiaohui Fan (Journal of Environmental Chemical Engineering, 2026)

Effects of recombinant carrot antifreeze protein concentrations on frozen dough and bread: Insights into dynamic changes of water and ice crystals - Ying Huang; Shenying Zhang; Haojia Zhu; Caiyun Liu; Zichen Huang; Hanzhang Hao; Yingxue Che; Mei Liu; Ying Liang; Xueling Zheng; Chong Liu; Limin Li (Food Chemistry, 2026)

Targeted photodynamic therapy for multispecies dental biofilms using liposome encapsulated p-Toluquinone - Chen Liang; Yongli Li; Zuan-Tao Lin; Zhilong Wang; Ya He; Yan Dong; Zihan Ran; Sophia Zhang; Ying Zhao; Songling Wang; Mei X. Wu (Chemical Engineering Journal, 2026)

Eight new dammarane-type triterpenoid saponins from Gynostemma pentaphyllum - Gang Li; Guang Yang; Xiao-juan Chen; Peng-xin Lu; Hai-zhen Liang; Mei-yan Wang; Jie Zhang; Bao-lin Guo; Bai-ping Ma (Natural Product Research, 2026)

Caseazins R−Y, cytotoxic podocarpane diterpenoids from Casearia kurzii - Xue-Wen Wu; Qiong Wei; Xia Pu; Chun-Mei Cha; Rui Li; Yin-Qiao Huang; Rui-Han Zhang; Xiao-Li Li; Hong-Liang Li; Wei-Lie Xiao (Phytochemistry, 2026)

Pinoresinol diglucoside alleviates hindlimb unloading-induced bone loss in mice - Ying-Ying Xuan; Liang Li; Yi Wu; Zhen-Long Wei; Mei Zhang; Min-Na Liu; Dong-Shuai Shen; Yu-Hai Gao; Cory J Xian; Hui-Ping Ma; Ke-Ming Chen (Life Sciences in Space Research, 2026)

A novel physics-guided collaborative modeling method for steady-state simulation of air source heat pump system - Lianyu Shan; Qingzhuang Wu; Mei Wang; Hui Zhang; Wenbo Li; Yanhua Guo; Shuangquan Shao; Zhuang Chen; Yaran Liang (International Journal of Refrigeration, 2026)

Oxidation behavior and mechanism of biomass-derived long-chain ethers via ReaxFF molecular dynamics simulation - Jin Li; Hao-Long Su; Zheng Mei; Ling-Chen Zhou; Fang-Chao Hou; Jing Sun; Liang Song (Biomass and Bioenergy, 2026)

Neutrophil extracellular traps in cardiovascular disease: a bibliometric analysis (2005–2024) - Li-Mei Liang; Xing Chen; Yan Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

7,8-Dihydroxyflavone attenuates cisplatin-induced cardiomyocyte apoptosis and mitochondrial dysfunction via the p53/Nrf2 pathway - Zhen Tian; Ting-ting Tan; Yu-wei Hu; Jia-tong Yao; Xiao-ting Kang; Jin-yu Zhou; Dong-xu Jia; Qing-liu Li; Ru-jin Liang; Li-mei Zhao; Hua Zhu; Jing Zhao; et al. (Toxicology and Applied Pharmacology, 2025)

An overview of the detection of P-phenylenediamine - Zhong Liang; Lei Liang; Tong Li; Yuncan He; Yu Zhang; Liujia Li; Yicheng Zhang; Lianrui Mei (Next Research, 2025)

DeepSANet: A deep learning approach for hierarchical geographical source attribution of Salmonella - Shan Liang; Shaohui Mei; Jiahao Ji; Bingkui Li; Mingyuan Xu; Miaomiao Chen; Yawen Huang; Yuxin Zheng; Di Chen; Xiangyu Deng; Shaoting Li; Hongmei Zhang (Food Research International, 2025)

Climatic influences on annual and intra-annual xylem anatomical traits of four coniferous tree species in the central Hengduan Mountains, Southwest China - Ju-Mei Zhang; Zaw Zaw; Pei-Li Fu; Shankar Panthi; Jambay Dema; Tong-Liang Xu; Hui Zhang; Achim Bräuning; Ze-Xin Fan (Dendrochronologia, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

High-throughput wheat seedling phenotyping via UAV-based semantic segmentation and ground sample distance driven pixel-to-area mapping - Honghao Zhou; Qing Li; Bingxi Qin; Haijiang Min; Shaowei Liang; Xiao Wang; Jian Cai; Qin Zhou; Mei Huang; Dong Jiang; Yingxin Zhong; Jiawei Chen (Computers and Electronics in Agriculture, 2025)

The optimization design for the truss substructure of the novel truss-type submerged floating tunnel using the topology optimization method - Junfeng Li; Zhiwen Wu; Canrong Xie; Liang Xiao; Ankit Garg; Guoxiong Mei (Ocean Engineering, 2025)

The spatial diversity of secondary organic carbon aerosols at the city level: insights from explainable machine learning - Xiaojian Xu; Cheng Wu; Chenglei Pei; Mei Li; Chunlei Cheng; Menghua Lu; Zhijiong Huang; Baoling Liang; Xinkun Fang; Mengxi Ye; Dui Wu (Atmospheric Environment, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

DTX1 Modulates Microglial M1 Polarization and Exacerbates Neuroinflammation in Traumatic Brain Injury Model Rats through NF—κB/IRF5 - Yonghui Zhang; Zongxing Zou; Rongwei Li; Xiaochuan Fu; Ganyu Li; Lu Wang; Yan Zhang; Yuyu Chen; Zuzhi Chen; Dongfang Yang; Yan Jiao; Weiguang Zhang; et al. (Molecular Neurobiology, 2025)

Oxymatrine possibly inhibits differentiation and maturation of oligodendrocytes in the remyelination of the toxin-induced demyelination animal model - Mei Li; Fei Huang; Jian Song; Renzhang Liang; Zhongwei Zhou; Yinglan Lin; Lili Hu; Jinghai Gu; Hua Yang; Shaozhang Hou; Huisheng Ma; Peng Wang (Metabolic Brain Disease, 2025)

Assessment of the ASM2d two-step nitrification model across different seasons: Parameter calibration, microbial analysis, and model validation - Shiyu Wang; Peng Mei; Hanying Liang; Peipei Shang; Peter A. Vanrolleghem; Yongmei Li (Journal of Environmental Chemical Engineering, 2025)

Dual-sulfur defects decorated 1T-WS2/Cd0.5Zn0.5S heterojunctions for boosted photocatalytic hydrogen evolution - Mei Dong; Wenjun Li; Liang Geng; Ruixue Huang; Hongli Han; Yuan Liu (Journal of Environmental Chemical Engineering, 2025)

Overshoot, potential air pollution co-benefits and food shortages - Li-Jing Liu; Qiao-Mei Liang; Felix Creutzig; Hua Tong; Yu-Xuan Xiao; Xiang-Yan Qian; Hao Wang; Si-Yi Wei; Xiao-Chen Yuan; Biying Yu; Lan-Cui Liu; Yi-Ming Wei (Global Environmental Change, 2025)

A 3D point cloud and deep learning based automated process for quantifying multi-scale phenotypes in sliced bread - Honghao Zhou; Jungao Zhang; Qin Zhou; Xinru Wang; Haijiang Min; Bingxi Qin; Shaowei Liang; Xiao Wang; Yingxin Zhong; Jian Cai; Mei Huang; Qing Li; et al. (Food Research International, 2025)

The role of N6-methyladenosine (m6A) modification in plants - Cui-Xian Qin; Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Miao Wang; You-Qiang Pan; Li Zhou; Bao-Qing Zhang; Jian-Hui Zhou; Dong-Liang Huang (Theoretical and Applied Genetics, 2025)

A heterogeneous lunar mantle revealed by young low-Ti mare basalt NWA 16460 - Weibiao Hsu; Aoxin Mei; Yukang Liang; Lei Jin; Kai Zhao; Lihui Chen; Shaolin Li; Chipui Tang (Science Bulletin, 2025)

Reductive transformation processes of ferrihydrite and U(VI) triggered by S2- under an anaerobic environment - Jiayu Song; Shirong Qiang; Huiyang Mei; Ping Li; Jianjun Liang; Qiaohui Fan (Journal of Hazardous Materials, 2025)

Effects of mulches on greenhouse gas emissions and soil microbial communities in cabbage production - Rong Liang; Lei Mei; Xuelian Fan; Jiangxing Wu; Mouliang Xiao; Yongfu Li; Jina Ding; Li Wang; Jaloliddin Shavkiev; David R. Chadwick; Davey Jones; Zhaofeng Yuan; et al. (Journal of Hazardous Materials, 2025)

Targeted discovery of oxygen-bridged sesquiterpenes from Cinnamomum migao by MS/MS-based molecular networking and their neuroprotective activities - Lang Zhou; Xiong Pan; Fa-ju Chen; Mei Peng; Yu Wang; Ming Gao; Li-shou Yang; Liang-qun Li; Juan Yang; Xiao-sheng Yang; Qi-ji Li (Phytochemistry, 2025)

Efficient caproate production from ethanol and acetate via chain elongation reinforced by Fe/Fe3O4 in mixed culture system - Cunsheng Zhang; Chengmei Li; Tianyu Liang; Min Li; Yuxuan Sun; Ziwei Chen; Mei Zhao; Xianghui Qi (Journal of Environmental Management, 2025)

Scandium and gallium in weathered basalts as unconventional resources - Mei-Fu Zhou; Wen Winston Zhao; Zhenchao Wang; Min Wang; Shengbiao Yang; Lei Meng; Liang Qi; Guangfu Xing; Xiang Li; Dai Zhou (Journal of Asian Earth Sciences, 2025)

Investigating the antifungal mechanism of Artemisia argyi essential oil against Botrytis cinerea, Alternaria alternata, and Penicillium digitatum and its application in extending blueberry shelf life - Yue-yan Chen; Yu-dong Zhang; Li Wang; Mei-qing Li; Yu Wang; Jin Liang; Dong-liang Wang; Hai-wei Zhang (International Journal of Food Microbiology, 2025)

Anti-aging effect of tea and its phytochemicals - Huijun Liang; Mei Qu; Song Ang; Dongli Li; Chengwei He (Food Research International, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Stage-specific phosphorus mobilization enhances phosphorus uptake in relay-intercropped soybean - Li Wang; Xiaoqian Chen; Bin Cheng; Huan Yang; Yang Gao; Xiuni Li; Mei Xu; Liang Yu; Yushan Wu; Tao Zhou; Weiguo Liu; Wenyu Yang (Agriculture, Ecosystems & Environment, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

In-situ hydrogen-mediated catalytic transfer hydrogenolysis of Kraft lignin for highly selective production of monomeric phenols - Han-Bing Gao; Bing-Hu Xie; Yue-Lun Wang; Le-Le Qiu; Yun-Peng Zhao; Jian Xiao; Mei Zhong; Jing Liang; Jian Li; Fang-Jing Liu; Jing-Pei Cao (Fuel, 2025)

Enhancing the performance of injectable self-activating PVA-alginate hydrogel by Ag@MXene nanozyme as NIR responsive and photoenhanced antibacterial platform for wound healing - Zepeng Liang; Zelin Sang; Yumei Li; Zhenhua Chen; Xifan Mei; Xiuli Ren (Carbohydrate Polymers, 2025)

Genome-Wide Identification and Characterization of NITRATE REGULATORY GENE 2 (NRG2) Family Genes in Brassica napus - Fanli Zhang; Yuquan Zhao; Lili Liu; Jinfeng Wu; Yaqian Chen; Yufang Li; Lichao Deng; Tonghua Wang; Liang Qu; Mei Li; Qijun Xie; Mingli Yan (Plant Molecular Biology Reporter, 2025)

Fate and transformation of psychotropic drugs in urban wastewater systems and receiving rivers via the integration of targeted and suspect screening analysis - An-Guo Wang; Jin-Na Zhang; Li-Xin Hu; You-Sheng Liu; Guang-Guo Ying; Yin-Xiu Liang; Mei-Ying Xu; Zhi-Qiang Yu (Water Research, 2025)

Tackling the carbon footprint of tourism: Strategies for China's inbound and domestic travel - Chao-Yun Zhong; Li-Jing Liu; Qiao-Mei Liang; Yan-Yan Yu (Resources, Conservation and Recycling, 2025)

N-acyl homoserine lactones - Modified anode improves carbamazepine removal in microbial fuel cells: Effect of electrogenic biofilm - Jing Fu; Xiang Li; Hao Chen; Jingting Mei; Liang Tang (Journal of Water Process Engineering, 2025)

Organic acid promoting the degradation of nonylphenol by persistent free radicals in biochar - Jie Ji; He Zhang; Feichao Zhang; Yao Wu; Han Zhang; Ziwei Mei; Wenxuan Zhou; Liang Li; Hong Tao; Meicheng Wen (Chemical Engineering Journal, 2025)

Interface selectivity-based biochar: Directional evolution of properties, application & carbon neutralization evaluation - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Mei Ru Yue; Yun Dong Liu; Bu Li; Jia Jie Zou; Jia Wang; Han Tang; Min-tian Gao; Yucang Liang; Wenjuan Wang; et al. (Chemical Engineering Journal, 2025)

Development of a shear strengthening conductive hydrogel for impact protection and distress signal emission - Juan Tan; Xi Li; Chuan Ru Zheng; Anna Tan; Xiu Chen Li; Hai Liang Ni; Wen Hao Yu; Yue Feng Bai; Ping Hu; Hong Mei Chen (Chemical Engineering Journal, 2025)

Three new dimeric 2-(2-phenethyl)chromones from the agarwood of Aquilaria malaccensis - Xian-Yun Yan; Wei Li; Hao Wang; Wen-Hua Dong; Jun Zeng; Fei Wu; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai (Phytochemistry Letters, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

Synergy between aerated drip and biodegradable film enhances sustainable maize production in arid oasis - Yonghui Liang; Mei Wu; Jinzhu Zhang; Zhanli Ma; Yue Han; Yue Wen; Rui Chen; Jian Liu; Haiqiang Li; Zhenhua Wang (European Journal of Agronomy, 2025)

A glycogen synthase kinase-3 gene enhances grain yield heterosis in semi-dwarf rapeseed - Li Bao; Liu Xinhong; Yang Qian; Zhang Hui; Tan Wenqing; Yan Mingli; Deng Lichao; Li Mei; Qu Liang; Guo Yiming (Plant Molecular Biology, 2025)

Dynamic proteome and acetylome profiling reveals key regulators of sucrose accumulation in sugarcane - Miao Wang; Ao-Mei Li; Zhong-Liang Chen; Cui-Xian Qin; Fen Liao; You-Qiang Pan; Prakash Lakshmanan; Xiao-Feng Li; Dong-Liang Huang (Plant Cell Reports, 2025)

Identifying critical riparian zones for eco-environmental management of the Yangtze River through pollution mapping - Biqing Xia; Sisi Li; Zhigang Mei; Wangzheng Shen; Menghan Mi; Ziqi Qiang; Liang Zhang (Journal of Environmental Management, 2025)

Untargeted qualitative and targeted quantitative analysis of saponins reveal differential chemotypes of Gynostemma pentaphyllum and G. longipes from different geographical origins - Hai-Zhen Liang; Mei-Yan Wang; Guang Yang; Gang Li; Jie Zhang; Lan Yao; Yi Nan; Chang-Liang Huang; Xiao-Juan Chen; Juan Song; Feng Cao; Bao-Lin Guo; et al. (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

In vivo self-assembled bispecific fluorescence probe for early detection of bladder cancer and metastasis - Da-Yong Hou; Ni-Yuan Zhang; Peng Zhang; Xiang-Peng Li; Jiong-Cheng Wu; Mei-Yu Lv; Zhi-Jia Wang; Xing-Jie Hu; Jian-Xiao Liang; Hong-Lei Wang; Yue-Ze Wang; Hui-Hui You; et al. (Science Bulletin, 2025)

Intelligent sensing platform based on europium-doped carbon dots for dual-functional detection of ciprofloxacin/Ga3+ and its tracking in vivo - Le Liang; Su-qian Cai; Yan-li Leng; Chan Huang; Yong-qing Liu; Ye Wang; Li Luo; Mei Han; Xiao-hong Li; Xiao-hua Cai (Journal of Hazardous Materials, 2025)

Yam glycoprotein promotes white adipose tissue browning, enhances metabolism, and boosts exercise tolerance in mice: A novel Strategy for metabolic disease prevention - Weiye Li; Yifeng Rang; Jian Shi; Meijuan Mei; Hongyong Qiu; Yan Liu; Boji Liang; Chunhong Liu (Food Bioscience, 2025)

Advanced fabrication of three-dimensional bicontinuous MXene/agarose composite monoliths for high-selective rapid separation of antibodies - Xiang-Dong Xu; Jing Li; Jun-Qi Zhang; Yuan Peng; Chen-Mei Sun; Ru-Qi Liang; Jian-Bo Qu (Chemical Engineering Journal, 2025)

High performance piperidinium based anion exchange membranes with different twisted backbone structures for fuel cells - Ying Jie Liu; Guo Liang Zhang; Yong Qi Hu; Hui Peng; Li Wei Lai; Ai Mei Zhu; Qiu Gen Zhang; Qing Lin Liu (Chemical Engineering Journal, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

A new isoflavone from the stems of Derris eriocarpa How - Ying Liu; Zhen-Xin Zhu; Yue Lu; Cong Wang; Hong-Cun Liu; Juan Meng; Jin Qi; Xiao-Ning Huang; Xiao-Mei Lu; Wen-Sen Lu; Shu-Han Luo; Hai-Na Liang; et al. (Natural Product Research, 2025)

Sequestration process and mechanism of U(VI) on montmorillonite-aspergillus niger composite - Rongyue Geng; Shirong Qiang; Huiyang Mei; Beihang Zhang; Ping Li; Jianjun Liang; Qiaohui Fan (Science of The Total Environment, 2025)

Stability of China's terrestrial ecosystems carbon sink during 2000-2020 - Liang Shi; Honglin He; Li Zhang; Junbang Wang; Xiaoli Ren; Guirui Yu; Peng Hou; Jixi Gao; Bin Chen; Keyu Qin; Lili Feng; Shaoqiang Wang; et al. (Resources, Conservation and Recycling, 2025)

A review of hydroxyapatite synthesis for heavy metal adsorption assisted by machine learning - Mengsi He; Zhuo Zhang; Mei Wang; Chouyuan Liang; Hejing Wang; Cheng Cheng; Yuanyuan Li; Yakun Wang; Ze Zhang (Journal of Hazardous Materials, 2025)

Enhancing butyrate synthesis and intestinal epithelial energy supply through mixed probiotic intervention in dextran sulfate sodium-induced colitis - Heng Zhang; Jingzhou Sun; Aowen Xie; Huiqin Yang; Yingjun Li; Yuxia Mei; Jinshan Li; Lei Xiao; Yangyang Liu; Yunxiang Liang (Food Bioscience, 2025)

Activation of 5-HT6 Receptors in the Ventrolateral Orbital Cortex Produces Anti-Anxiodepressive Effects in a Rat Model of Neuropathic Pain - Yu-Long Zhao; Hui-Yuan Yi; Sani Sa’idu Baba; Yi-Xiao Guo; Xiao-Cui Yuan; Xue-Mei Hou; Ling-Li Liang; Fu-Quan Huo (Molecular Neurobiology, 2025)

Sponge-based FeS activated persulfate coupled with biodegradation for highly efficient removal of tetracycline: Batch and column validation - Shou Mei; Mengyao Han; Jintao Hao; Yuxuan Ye; Yuwei Deng; Luxin Liang; Ziyi Zhan; Rongling Wang; Xuanyuan Pei; Qiang Li; Zhenbin Wu; Fei Pan (Journal of Water Process Engineering, 2024)

Multi-stimuli geminate encryption based on triphenylethylene for advanced anti-counterfeiting - Zhuo-Cheng Li; Zuo-Qin Liang; Zi-Hang Zhang; Su-Hang Xu; Pu Wang; Guo-Liang Dai; Chang-Qing Ye; Xiao-Mei Wang (Chemical Engineering Journal, 2024)

A novel variant (p.A524P) in Spastin is responsible for a Chinese family with hereditary spastic paraplegia - Yu-Han Jin; Yang-Ziyu Xiang; Mei-Fang Zhao; Yi-Hui Liu; Liang-Liang Fan; Xiao-Cong Li (Molecular Biology Reports, 2024)

The response of daytime nitrate formation to source emissions reduction based on chemical kinetic and thermodynamic model - Yuting Wei; Dongheng Zhao; Zhang Zhang; Mei Li; Feng Wang; Chenglei Pei; Danni Liang; Yinchang Feng; Guoliang Shi (Science of The Total Environment, 2024)

Effect of wheat flour particle size on the quality deterioration of quick-frozen dumpling wrappers during freeze-thawed cycles - Lulu Yin; Xinyue Wu; Guolan Qin; Jiajing Han; Mei Liu; Yangkun Wei; Ying Liang; Jin Zhang; Shenying Zhang; Haojia Zhu; Ying Huang; Xueling Zheng; et al. (Food Research International, 2024)

Green massive mechanical synthesis of highly efficient Zn-Doped Cs3Cu2I5 for LED and X-ray imaging applications - Qi-Hua Yang; Gui-Hua Li; Yu-Chen Ao; Shu-Juan Zhao; Han-Qi Wei; Le Fu; Zhi-Wei Luo; Tian-Liang Zhou; Chu-Jie Wang; Ge-Mei Cai (Chemical Engineering Journal, 2024)

Agricultural management reshaped the diversity patterns and community assembly of rhizosphere bacterial communities in a desert farming system - Wen-Hui Lian; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Zhi-Liang Lin; Chao-Jian Hu; Jia-Rui Han; Wen-Jun Li; Lei Dong (Applied Soil Ecology, 2024)

Robust sensor selection based on maximum correntropy criterion for ocean data reconstruction - Qiannan Zhang; Huafeng Wu; Li’nian Liang; Xiaojun Mei; Jiangfeng Xian (Frontiers in Marine Science, 2024)
Selecting an optimal subset of sensors that can accurately reconstruct the full state of the ocean can reduce the cost of the monitoring system and improve monitoring efficiency. Typically, in data-driven sensor selection processes, the use of Euclidean distance to evaluate reconstruction error is susceptible to non-Gaussian noise and outliers present in ocean data. This paper proposes a Robust Sensor Selection (RSS) evaluation model based on the Maximum Correntropy Criterion (MCC) through subspace learning, enabling the selection of robust sensor measurement subsets and comprehensive data reconstruction. To more accurately quantify the impact of varying noise magnitudes, noise weights were incorporated into the model’s objective function. Additionally, the local geometric structure of data samples is utilized to further enhance reconstruction accuracy through the selected sensors. Subsequently, the MCC_RSS algorithm is proposed, which employs the Block Coordinate Update (BCU) method to achieve the optimal solution for the proposed model. Experiments conducted using ocean temperature and salinity datasets validate the proposed MCC_RSS algorithm. The results demonstrate that the sensor selection method proposed in this paper exhibits strong robustness, outperforming comparative methods under varying proportions of outliers and non-Gaussian noise.

Biodegradation of phthalic acid esters by a novel marine bacterial strain RL-BY03: Characterization, metabolic pathway, bioaugmentation and genome analysis - Lei Ren; Xingjia Wang; John L. Zhou; Yang Jia; Hanqiao Hu; Chengyong Li; Zhong Lin; Mei Liang; Yanyan Wang (Chemosphere, 2024)

Precipitation contributes to alleviating pollution of rubber-derived chemicals in receiving watersheds: Combining confluent stormwater runoff from different functional areas - Yue-Hong Liu; Yu-Xian Mei; Jing-Yi Wang; Shan-Shan Chen; Jia-Li Chen; Nan Li; Wang-Rong Liu; Jian-Liang Zhao; Qian-Qian Zhang; Guang-Guo Ying (Water Research, 2024)

Synthesis of a novel double Z-scheme BiVO4/Cu2O/g-C3N4 sonocatalyst and research on sonocatalytic degradation of tetracycline - Yang-Cheng Liu; Ying-Di Ge; Hui-Li An; Wan-Ting Ju; Xin-Yi Zhou; Mei-Yi Xing; Yang Wang; Lin Zhang; Xin Wang; Liang Xu (Journal of Environmental Chemical Engineering, 2024)

Combined effects of nitrogen limitation and overexpression of malic enzyme gene on lipid accumulation in Dunaliella parva - Shi-Yu Liang; Li-Hua Li; Meng-Xiang Ling; Lei Mo; Li-Mei Huang; Ling-Ru Ruan; Chang-Hua Shang (Bioresource Technology, 2024)

Nanoscale phase management of the 2D/3D heterostructure toward efficient perovskite solar cells - Hao Gu; Annan Zhu; Junmin Xia; Wang Li; Jiahao Zheng; Tao Yang; Shengwen Li; Nan Zhang; Shiliang Mei; Yongqing Cai; Shi Chen; Chao Liang; et al. (Science Bulletin, 2024)

Pressure–temperature evolution, protolith characteristics and tectonic setting of granulite facies rocks from Laojinchang area in the Longgang Block, China - Mei-hui Li; Chen-yue Liang; Chang-qing Zheng; Bo Wang; Ding Ban; Zi-jing Zhang (Precambrian Research, 2024)

Prevalence and Antibiotic Resistance Patterns of Methicillin-Resistant Staphylococcus aureus (MRSA) in a Hospital Setting: A Retrospective Study from 2018 to 2022 - Tian Lan; Bin Zhang; Jin Lu Liu; Qian Jia; Jing Gao; Liang Cao; Juan Yan; Bao Liang Li; Xiao Juan Xie; Yu Huan Xu; Hong Mei Wen (Indian Journal of Microbiology, 2024)

Shrub expansion increases nitrification and denitrification in alpine meadow soils - Yu-Chen Zhang; Bin Jia; Jie Chen; Yan-Mei Liang; Li Jia; Zhen-Huan Guan; Min Wei; Zhanhuan Shang; Xiao Gang Li (Applied Soil Ecology, 2024)

Effects of Enterobacter cloacae insecticidal protein on the Duox-ROS system and midgut bacterial community and function of Galleria mellonella larvae - Tao Zhu; Yi Yang; Chao Hu; Liang Ma; Jiaqing Sheng; Ruiying Chang; Yanfei Liao; Lianzhe Wang; Yutao Zhu; Mei Zhao; Bingbing Li; Taotao Li; et al. (Toxicon, 2024)

Highly efficient adsorption and removal of Cd(II) from wastewater by mass synthesis of magnetically functionalized UiO-66 based on its high coordination advantage - Mei Li; Kaixun Tian; Sijia Liu; Pei Liang; Wenzi Xiong; Xiyu Yao (Chemical Engineering Journal, 2024)

Development of Sugar Industry in China: R&D Priorities for Sustainable Sugarcane Production - Yang-Rui Li; Bao-Qing Zhang; Xiu-Peng Song; Qiang Liang; Krishan K. Verma; Dong-Mei Li (Sugar Tech, 2024)

A Robust Sparse Sensor Placement Strategy Based on Indicators of Noise for Ocean Monitoring - Qiannan Zhang; Huafeng Wu; Li’nian Liang; Xiaojun Mei; Jiangfeng Xian; Yuanyuan Zhang (Journal of Marine Science and Engineering, 2024)
A well-performing data-driven sparse sensor deployment strategy is critical for marine monitoring systems, as it enables the optimal reconstruction of marine physical quantities with fewer sensors. However, ocean data typically contain substantial amounts of noise, including outliers (incomplete data) and inherent measurement noise, which heightens the complexity of sensor deployment. Therefore, this study optimizes the sparse sensor placement model by establishing noise indicators, including small noise weight and large noise weight, which are measured by entropy to minimize the prediction bias. Building on this, a robust sparse sensor placement algorithm is proposed, which utilizes the block coordinate update (BCU) iteration method to solve the function. During the iterative updating process, the proposed algorithm simultaneously updates the selection matrix, reconstruction matrix, and noise matrix. This allows for effective identification and mitigation of noise in the data through evaluation. Consequently, the deployed sensors achieve superior reconstruction performance compared to other deployment methods that do not incorporate noise evaluation. Experiments are also conducted on datasets of sea surface temperature (SST) and global ocean salinity, which demonstrate that our strategy significantly outperforms several other considered methods in terms of reconstruction accuracy while enabling autonomous sensor deployment under noisy conditions.

Defect-decorated Cu2MoS4 as a new efficient hydrogen evolution cocatalyst: Rich active sites, rapid charge transfer and optimized hydrogen adsorption - Mei Dong; Wenjun Li; Liang Geng; Xiaohui Ma; Yajie Li; Yueyan Fan; Ajmal Khan (Fuel, 2024)

Potential structure–function relationships of pectic polysaccharides from quinoa microgreens: Impact of various esterification degrees - Jie Li; Jing Feng; Xiao Luo; Mei-Mei Qu Mo; Wen-Bing Li; Jing-Wei Huang; Shengpeng Wang; Yi-Chen Hu; Liang Zou; Ding-Tao Wu (Food Research International, 2024)

Seasonal variations and sources of atmospheric EPFRs in a megacity in severe cold region: Implications for the influence of strong coal and biomass combustion - Shi-Ming Jia; Mei-Hong Chen; Pu-Fei Yang; Liang Wang; Guo-Ying Wang; Li-Yan Liu; Wan-Li Ma (Environmental Research, 2024)

Elevated nitrogen loadings facilitate carbon dioxide emissions from urban inland waters - Yong-Mei Hou; Fu-Jun Yue; Si-Liang Li; Xiao-Long Liu (Journal of Environmental Management, 2024)

C@MOF composite material for rapid and efficient capture of gaseous iodine - Rui-Li Yu; Mei-Qi Sun; Xiao-Yu Wang; Dao-Tong Li; Zhen-Le Li; Liang-Zhi Xia (Chemical Engineering Journal, 2024)

Sugarcane borers: species, distribution, damage and management options - Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Yong Zhao; Cui-Xian Qin; Miao Wang; You-Qiang Pan; Shao-Long Wei; Dong-Liang Huang (Journal of Pest Science, 2024)
Lepidopteran borers stand out as the most destructive pests in sugarcane, leading to reductions in stalk weight, juice quality and sugar recovery. Presently, integrated pest management (IPM) systems are utilized for sugarcane borer management, employing diverse methods encompassing cropping system, chemical pesticides, behavioral manipulation, biological agents and the selection of resistant varieties. However, the effectiveness of this strategy remains controversial due to concerns about harmful residues, formulation limitations, environmental variability, labor shortages and increased input costs. Currently, multiple lines of transgenic sugarcane expressing insecticidal genes from the bacterium Bacillus thuringiensis (Bt) have been developed globally, offering the prospect of increases production with reduced pesticides application, thereby eliminating the negative effect of IPM. In Brazil, the first genetically modified sugarcane cultivars resistant to the sugarcane borer have been approved and released for commercial cultivation, shedding a bright light on a viable solution for sugarcane borers. This paper reviews borer species and distribution, the significant damage caused by sugarcane borers, current control approaches and the future effective control strategies. Additionally, this work provides comprehensive understanding on Bt sugarcane, serving as an additional tool to complement conventional sugarcane borers control resistance programs.

Microbial mediation of soil carbon loss at the potential climax of alpine grassland under warming - Zhengxiong Liang; Xue Guo; Suo Liu; Yifan Su; Yufei Zeng; Changyi Xie; Qun Gao; Jiesi Lei; Baochan Li; Mei Wang; Tianjiao Dai; Liyuan Ma; et al. (Soil Biology and Biochemistry, 2024)

Mechanistic insight into the degradation of sulfadiazine by electro-Fenton system: Role of different reactive species - Yanshi Zheng; Jinyan Yang; Mei Li; Yingshi Zhu; Jiayu Liang; Dehai Yu; Ziyao Wang; Jianchuan Pei (Journal of Hazardous Materials, 2024)

The effects of different drying methods on the flavor profile of wheat germ using E-nose and GC-IMS - Yang Zhong; Gexing Zhang; Fangqin Zhang; Shuting Lin; Mei Wang; Yue Sun; Jin Liang; Xueling Li (Journal of Cereal Science, 2024)

An Hsp70 promoter–based mouse for heat shock–induced gene modulation - Hangang Chen; Yangli Xie; Mei Zhang; Junlan Huang; Wanling Jiang; Ruobin Zhang; Can Li; Xiaolan Du; Hua Chen; Qiang Nie; Sen Liang; Qiaoyan Tan; et al. (Journal of Molecular Medicine, 2024)

Unveiling combined ecotoxicity: Interactions and impacts of engineered nanoparticles and PPCPs - Xiang Li; Liyan Li; Liang Tang; Jingting Mei; Jing Fu (Science of The Total Environment, 2024)

Structurally diverse cucurbitane-type triterpenoids from the tubers of Hemsleya chinensis with cytotoxic activity - Xiao-San Li; Qi-Lin Wang; Zhi-Peng Xu; Ming-Shang Liu; Xiao-Yan Liang; Jia-Chon Zheng; Hong-Yao Deng; Li Liu; Yong-Mei Huang; Mao-Xun Yang; Xue-Mei Yang (Phytochemistry, 2024)

Phylogenomic analyses sheds new light on the phylogeny and diversification of Corydalis DC. in Himalaya–Hengduan Mountains and adjacent regions - Yan-Yan Liu; Jia-Liang Cao; Sheng-Long Kan; Peng-Hang Wang; Jun-Li Wang; Ya-Nan Cao; Hong-Wei Wang; Jia-Mei Li (Molecular Phylogenetics and Evolution, 2024)

Effect of vent area on vented ammonia-hydrogen-air deflagrations in a 1-m-long duct - Shikai Huang; Jin Guo; Liang Mei; Zexuan Yang; Hongyan Wang; Yiming Li (Fuel, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Spatial and widely targeted metabolomics and anatomical analysis reveal the mechanisms associated with petal bicolor patterning of two Dendrobium species - Mei-Jing Ou; Hong-Yan Li; Han Liang; Zhen-Hai Deng; Zi-Bin Zhang; Jia-Wei Li (Brazilian Journal of Botany, 2024)

A proteomic study on gastric impairment in rats caused by microcystin-LR - Shang-Chun Li; Li-Hong Gu; Yan-Fang Wang; Li-Mei Wang; Liang Chen; John P. Giesy; Xun Tuo; Wen-Li Xu; Qian-Hui Wu; Yi-Qing Liu; Ming-Huo Wu; Yang-Yang Diao; et al. (Science of The Total Environment, 2024)

Baicalin − 2- ethoxyethyl ester alleviates renal fibrosis by inhibiting PI3K/AKT/NF-κB signaling pathway - Jiacun Li; Ke Zhang; Mei Xu; Huanyue Cui; Yaping Guo; Dahong Yao; Wenhua Chen; Huaimin Liang; Hangyu Wang; Jinhui Wang (Toxicology and Applied Pharmacology, 2024)

Integrating carbon mitigation, PM2.5 reduction, and livelihood improvement: A non-equilibrium dynamic urban analysis in Beijing - Li-Jing Liu; Qiao-Mei Liang; Lan Wei (Sustainable Cities and Society, 2024)

Enhancing soil carbon and nitrogen through grassland conversion from degraded croplands in China: Assessing magnitudes and identifying key drivers of phosphorus reduction - Yuan Li; Ying Li; Qingping Zhang; Gang Xu; Guopeng Liang; Dong-Gill Kim; Carmen Rosa Carmona; Mei Yang; Jianming Xue; Yangzhou Xiang; Bin Yao; Yuying Shen (Soil and Tillage Research, 2024)

Bright photoactivatable probes based on triphenylethylene for Cu2+ detection in tap water and tea samples - Zuo-Qin Liang; Dong-Dong Song; Zhuo-Cheng Li; Su-Hang Xu; Guo-Liang Dai; Chang-Qing Ye; Xiao-Mei Wang; Xu-Tang Tao (Food Chemistry, 2024)

Revitalizing mitochondrial function and empowering spinal cord recovery using copper-catalyzed Pdots - Bao-Feng Zhao; Fan Wang; Jia-Chen Sun; Jin-Peng Gao; Li-Juan Zhao; Zhao-Liang Shen; Zhi-Peng Li; Yi-Xuan Wang; Yuan Wang; Dan Li; Xi-Fan Mei (Chemical Engineering Journal, 2024)

Correlational analysis of physicochemical indexes, microbial communities, and volatile components in light-flavor Daqu from north and south regions of China - Qi Yu; Feiyan Mou; Junwen Xiao; Cheng Zhan; Liang Li; Xu Chang; Xiaoyuan Dong; Maobin Chen; Xinrui Wang; Mei Chen; Shangling Fang (World Journal of Microbiology and Biotechnology, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Oncogenic and immunological roles of RACGAP1 in pan-cancer and its potential value in nasopharyngeal carcinoma - Cheng-shan Zheng; Wei-mei Huang; Hong-mei Xia; Jing-lin Mi; Yuan-qing Li; Hui-qing Liang; Li Zhou; Zhou-xue Lu; Fang Wu (Apoptosis, 2024)

Three new cardenolides from the fruits of Cascabela thevetia (L.) Lippold and their cytotoxic activities - Juan Long; Jia-Cheng Ouyang; Yu-Hao Luo; Qi-Jing Wu; Xiao-Tong Liao; Zhi-Le Chen; Qi-Lin Wang; Xiao-Yan Liang; Li Liu; Xue-Mei Yang; Xiao-San Li (Natural Product Research, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

Mechanism of Antidepressant Action of (2R,6R)-6-Hydroxynorketamine (HNK) and Its Compounds: Insights from Proteomic Analysis - Chaohui Zhen; Chong Wang; Yanjun Ma; Yuli Pang; Feiyue Cai; Jiali Meng; Yuefei He; Ping Xiao; Jianxi Liu; Xi Mei; Shupeng Li; Guanzheng Wu; et al. (Molecular Neurobiology, 2024)

Two new eudesmane sesquiterpenoids with neuroprotective activity from Pogostemon cablin - Qi Zheng; Chuan Ma; Liang Xiong; Cheng Peng; Li Guo; Da-Le Guo; E Zhao; Qin-Mei Zhou; Ou Dai (Phytochemistry Letters, 2023)

Enhanced expression of RAGE/NADPH oxidase signaling pathway and increased level of oxidative stress in brains of rats with chronic fluorosis and the protective effects of blockers - Yan-Lin Ma; Jie Deng; Ting Zhang; Hong-Mei Li; Qiu-Zhe Liang; Kai-Lin Zhang (Journal of Trace Elements in Medicine and Biology, 2023)

Development and characterization of self-emulsifying high internal phase emulsions using endogenous phospholipids from Antarctic krill oil - Dong-wen Fu; Jing-jing Li; Dong-mei Dai; Da-yong Zhou; Bei-wei Zhu; Liang Song (Food Chemistry, 2023)

Controllable reduction of absorbance and two-step reaction for 3D-printed SiC ceramics with micron-level periodic structure - Dou Yang; Hao Li; Wenqiang Yang; Minggang Zhang; Hui Mei; Shixiang Zhou; Jin Zhao; Tong Zhao; Yuekai Yan; Chengyu Liang; Lei Qiao; Laifei Cheng; et al. (Chemical Engineering Journal, 2023)

Constructing DNA Fingerprinting and Evaluating Genetic Diversity Among Sugar Beet (Beta vulgaris L.) Varieties Based on Four Molecular Markers - Xue-Mei Liang; Zhi Pi; Ze-Dong Wu; Sheng-Nan Li (Sugar Tech, 2023)

Correction to: The Domestic Isolation of Terbinafine- and Itraconazole Resistant Trichophyton indotineae in Chinese Mainland - Xue Kong; Ge Song; Huan Mei; Hailin Zheng; Chao Tang; Sybren de Hoog; Xiaofang Li; Xiaodong She; Weida Liu; Guanzhao Liang (Mycopathologia, 2023)

Environmental pollutants induce NLRP3 inflammasome activation and pyroptosis: Roles and mechanisms in various diseases - Yu Mou; Wenhao Liao; Yun Liang; Yuchen Li; Mei Zhao; Yaoyao Guo; Qin Sun; Jianyuan Tang; Zhilei Wang (Science of The Total Environment, 2023)

3D hierarchical fireproof gel polymer electrolyte towards high-performance and comprehensive safety lithium-ion batteries - Yirou Du; Xianshuai Liu; Lin Chen; Sihao Yin; Yuhui Xie; Ao Li; Xiaodong Liang; Yong Luo; Feng Wu; Yi Mei; Delong Xie (Chemical Engineering Journal, 2023)

Hybrid chain reaction and selective recognition-based homogeneous dual-fluorescence analysis of circulating tumor cells in clinical ovarian cancer samples - Qian Hu; Dan Tang; Mei Li; Xiaodu Liang; Juan Zhou; Yanming Meng; Yinhao Wei; Shixin Yan; Ruoyu Lin; Xiaoyu Niu; Lin Zhang (Analytica Chimica Acta, 2023)

Synergistic impact of co-exposures to whole blood metals on chronic kidney disease in general US adults: a cross‑sectional study of the National Health and Nutrition Examination Survey 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Wen-wen Bao; Yu-shan Zhang; Li-xin Hu; Shan Huang; Nan Jiang; Shao-yi Huang; Xue-ya Pu; Guang-hui Dong; Ya-jun Chen (Environmental Science and Pollution Research, 2023)

Secondary aerosol formation in incense burning particles by O3 and OH oxidation via single particle mixing state analysis - Zhancong Liang; Liyuan Zhou; Xinyue Li; Rosemarie Ann Infante Cuevas; Rongzhi Tang; Mei Li; Chunlei Cheng; Yangxi Chu; Patrick K.H. Lee; Alvin C.K. Lai; Chak K. Chan (Science of The Total Environment, 2023)

Effect of intense rainfall and high riverine water level on compound flood hazards in a river-valley city: A case study of Yingde, China - Liang Gao; Jiangpeng Mei; Jinhui Li; Wensheng Zhang; Chengguang Lai (Journal of Hydrology, 2023)

Uncovering PM2.5 transport trajectories and sources at district within city scale - Mei Shan; Yuan Wang; Yaling Lu; Chen Liang; Tingyu Wang; Linyan Li; Rita Yi-man Li (Journal of Cleaner Production, 2023)

Overlooked inorganic DBPs in trichloroisocyanuric acid (TCCA) disinfected indoor swimming pool: Evidences from concentration, cytotoxicity, and human health risk - Jiafu Li; Jingsi Chen; Zhiyong Hu; Xinyu Li; Mei Li; Yuan Wang; Zengli Zhang; Xiaojun Liang (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

From promoting aggregation to enhancing obstruction: A negative feedback regulatory mechanism of alleviation of trivalent chromium toxicity by silicon in rice - Zhihao Pang; Yuchao Mei; Nina Nikolic; Miroslav Nikolic; Tingqiang Li; Hongyun Peng; Yongchao Liang (Journal of Hazardous Materials, 2023)

Low-dose benzo[a]pyrene exposure induces hepatic lipid deposition through LCMT1/PP2Ac-mediated autophagy inhibition - Yunqing Li; NingJing Liang; Tingting Tang; Zhijian Zheng; Muting Chen; Jiao Mo; Ning Zhang; Simi Liao; Yu Lei; Yijie Wu; Chunhua Lan; Huan Ding; et al. (Food and Chemical Toxicology, 2023)

The occurrence and probabilistic risk assessment of 3-MCPDEs and GEs in infant formulas from Chinese market employing Monte Carlo simulation technique - Zhengchao Shen; Kexin Tian; Muhammad Mujahid Ali; Sifan Mei; Xin Ma; Jiang Liang; Feng Pan; Jianwen Li; Haixia Sui; Zhenxia Du (Food and Chemical Toxicology, 2023)

The global burden of schizophrenia and the impact of urbanization during 1990–2019: An analysis of the global burden of disease study 2019 - Xuanxuan Li; Ning Wei; Jian Song; Jintao Liu; Jiajun Yuan; Rong Song; Li Liu; Lu Mei; Shuangshuang Yan; Yudong Wu; Rubing Pan; Weizhuo Yi; et al. (Environmental Research, 2023)

The associations of non-essential metal mixture with fasting plasma glucose among Chinese older adults without diabetes - Jing-Yuan Lei; Pan-Pan Wang; Hong-Li Wang; Yuan Wang; Liang Sun; Bing Hu; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; Chun-Mei Liang; Fang-Biao Tao; Lin-Sheng Yang; et al. (Environmental Science and Pollution Research, 2023)

Joint effect of whole blood metals exposure with dyslipidemia in representative US adults in NHANES 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Li-xin Hu; Wen-wen Bao; Yu-shan Zhang; Aerziguli Kakaer; Yu Zhao; Yi-can Chen; Xue-ya Pu; Shao-yi Huang; Nan Jiang; et al. (Environmental Science and Pollution Research, 2023)

Heterogeneous Fenton water purification catalyzed by iron phosphide (FeP) - Shu-Chuan Mei; Liang Li; Gui-Xiang Huang; Xiao-Qiang Pan; Han-Qing Yu (Water Research, 2023)

Potentially important regolith-hosted Sc deposits related to alkaline igneous complexes of the Permian Emeishan large igneous Province, SW China - Wen Winston Zhao; Mei-Fu Zhou; Zhengchao Wang; Yan Hei Martin Li; Liang Qi; Wei Terry Chen; Yu Shen (Journal of Asian Earth Sciences, 2023)

Influence of disinfection techniques on aliphatic disinfection byproduct formation and cytotoxicity/genotoxicity in swimming pools: A review - Tian Qiu; Zengli Zhang; Mei Li; Xiaojun Liang; Jiafu Li (Chemical Engineering Journal, 2023)

Material genome approach-based design of multi-functional self-curing epoxy resin with intrinsic flame retardancy and ultra-high modulus - Junliang He; Ji Zhou; Jizhen Tian; Shuai Li; Yunfei Gao; Zhengguang Heng; Yang Chen; Huawei Zou; Mei Liang (Chemical Engineering Journal, 2023)

The Domestic Isolation of Terbinafine- and Itraconazole-Resistant Trichophyton indotineae in Chinese Mainland - Xue Kong; Ge Song; Huan Mei; Hailin Zheng; Chao Tang; Sybren de Hoog; Xiaofang Li; Xiaodong She; Weida Liu; Guanzhao Liang (Mycopathologia, 2023)

The ratio of monocyte count and high-density lipoprotein cholesterol mediates the association between urinary tungsten and cardiovascular disease: a study from NHANES 2005–2018 - Yudong Wu; Yajie Meng; Weizhuo Yi; Rubing Pan; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; Xiaoni Sun; Shuangshuang Yan; Lu Mei; Jian Song; Shasha Song; et al. (Environmental Science and Pollution Research, 2023)

A novel DVAPSO-LSTSVM classifier in compressed sensing domain for intelligent pipeline leakage diagnosis - Shuaiyong Li; Zhengxu Dai; Mengqian Cai; Liang Liu; Lin Mei (Process Safety and Environmental Protection, 2023)

Dynamic analysis of layered soil-pile interaction based on the nearly continuous model - Xin Liu; Lixing Wang; M. Hesham El Naggar; Wenbing Wu; Hao Liu; Lichen Li; Kuihua Wang; Guoxiong Mei; Liang Xiao (Ocean Engineering, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Characterization of airborne microplastics at different workplaces of the poly(ethylene:propylene:diene) (EPDM) rubber industry - Xiaoni Sun; Rong Song; Jintao Liu; Shuangshuang Yan; Yuxuan Li; Xiaoyu Jin; Yunfeng Liang; Yudong Wu; Lu Mei; Rubing Pan; Weizhuo Yi; Jian Song; et al. (Environmental Science and Pollution Research, 2023)

Ancestors of Ulmus parvifolia from late Miocene sediments in Yunnan, Southwest China and its future distribution - Ping Lu; Jian-Wei Zhang; Xiao-Qing Liang; Hong-Mei Li; De-Liang Li (Review of Palaeobotany and Palynology, 2023)

Spatiotemporal changes of agricultural water footprint and its driving factors using the ARDL model in the Hexi corridor, China - Jun Zhang; Hui-xia Yang; Fan Zhou; Jia-liang Li; Dong-mei Zhou; Guo-zhang Cen; Jing Ma; Xiao-yan Zhu (Journal of Arid Environments, 2023)

Built environment and schizophrenia re-hospitalization risk in China: A cohort study - Jian Song; Yunfeng Liang; Zhiwei Xu; Yudong Wu; Shuangshuang Yan; Lu Mei; Xiaoni Sun; Yuxuan Li; Xiaoyu Jin; Weizhuo Yi; Rubing Pan; Jian Cheng; et al. (Environmental Research, 2023)

Schisandrin B Improves the Hypothermic Preservation of Celsior Solution in Human Umbilical Cord Mesenchymal Stem Cells - Ying Zhang; Peng Wang; Mei-xian Jin; Ying-qi Zhou; Liang Ye; Xiao-juan Zhu; Hui-fang Li; Ming Zhou; Yang Li; Shao Li; Kang-yan Liang; Yi Wang; et al. (Tissue Engineering and Regenerative Medicine, 2023)

Physicochemical Characterization of Three Active Pharmaceutical Ingredients for Compound Glycyrrhizin Solid Formulation and Compatibility Analysis via Thermal and Non-thermal Techniques - Xiang-yun Xie; Zhan-ying Chang; Chun-li Chen; Liang Zhang; Mei Wang; Cheng Tang; Hong-rui Xue; Xiao-li Gao (Journal of Pharmaceutical Innovation, 2023)

Sunshine duration and risks of schizophrenia hospitalizations in main urban area: Do built environments modify the association? - Li Liu; Qing Wu; Xuanxuan Li; Rong Song; Ning Wei; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Molecular characterization and antimicrobial activity of NK-lysin in black scraper (Thamnaconus modestus) - Mei-Yi Liu; Yi-Rong Zhang; Jian-Hua Zhang; Liang Miao; Yun-Fei Dang; Chen-Jie Fei; Chang-Hong Li; Jiong Chen (Fish & Shellfish Immunology, 2023)

Impact of crop types and irrigation on soil moisture downscaling in water-stressed cropland regions - Yu Wang; Ruonan Li; Mei Liang; Jinfeng Ma; Yanzheng Yang; Hua Zheng (Environmental Impact Assessment Review, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

The effect of phthalates exposure during pregnancy on asthma in infants aged 0 to 36 months: a birth cohort study - Jian-Qing Wang; Chun-Mei Liang; Ya-Bin Hu; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Peng Zhu; Jia-Hu Hao; Fang-Biao Tao (Environmental Geochemistry and Health, 2023)

Numerical Analysis of Propeller Wake Evolution under Different Advance Coefficients - Duo Yu; Yu Zhao; Mei Li; Haitian Liu; Suoxian Yang; Liang Wang (Journal of Marine Science and Engineering, 2023)
Propeller wake fields in an open-water configuration were compared between two loading circumstances using large-eddy simulation (LES) with a computational domain of 48 million grids and an overset mesh technique. To validate the results of the numerical simulation, available experimental data are compared, which indicates that the grid systems are suitable for the present study. The results indicate that the present LES simulations describe the inertial frequency range well for both high and low-loading conditions. Under high-loading conditions, the interlaced spirals and secondary vortices that connect adjacent tip vortices amplify the effects of mutual inductance, ultimately triggering the breakdown of the propeller wake systems. At a great distance from the propeller, the vortex system loses all coherence and turns into a collection of smaller vortices that are equally scattered across the wake. In contrast, under light-loading conditions, the wake vortex system exhibits strong coherence and has a relatively simple topology. The elliptic instability and pairing processes are only observed at a far distance from the propeller. The convection velocity transferring tip vortices downstream is larger under the light-loading condition, which leads to the larger pitch of the helicoidal vortices. The larger pitch weakens the mutual inductance or interaction effects among tip vortices, which delays the instability behaviors of the whole vortex system. The results and implications of this study serve as a guide for the development and improvement of next-generation propellers that function optimally when operating behind aquaculture vessels.

A pair of new oxindole alkaloids isolated from Uncaria macrophylla - Xin-Xin Liang; Jin-Xuan Yang; Jian-Mei Li; Jia-Bi Huang; Liu-Meng Yang; Tian-Tian Sun; Rong-Hua Luo; Wei-Lie Xiao; Yong-Tang Zheng; Xiao-Li Li (Natural Product Research, 2023)

Aristolochic acid I promotes the invasion and migration of hepatocellular carcinoma cells by activating the C3a/C3aR complement system - Yu Li; Sirui Zhu; Mei Xue; Ye Jing; Xiaoli Liu; Danhong Cai; Ye Zhao; Yaoyao Bian; Zhaofeng Zhang; Liang Zhang (Toxicology Letters, 2023)

Regional-modal optimization problems and corresponding normal search particle swarm optimization algorithm - Yi-li Yuan; Chang-ming Hu; Liang Li; Yuan Mei; Xue-yan Wang (Swarm and Evolutionary Computation, 2023)

Associations of polycyclic aromatic hydrocarbons, water-soluble ions and metals in PM2.5 with liver function: Evidence from schizophrenia cohort - Weizhuo Yi; Jun Cheng; Jian Song; Rubing Pan; Yunfeng Liang; Xiaoni Sun; Yuxuan Li; Yudong Wu; Shuangshuang Yan; Xiaoyu Jin; Lu Mei; Jian Cheng; et al. (Science of The Total Environment, 2023)

Chronic exposure to environmentally relevant concentrations of carbamazepine interferes with anxiety response of adult female zebrafish through GABA /5-HT pathway and HPI axis - Cheng-Ting Xie; Mei-Ling Tan; Ying-Wen Li; Qi-Liang Chen; Yan-Jun Shen; Zhi-Hao Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

In Vitro Antifungal Activity of Azoles and Other Antifungal Agents Against Pathogenic Yeasts from Vulvovaginal Candidiasis in China - Siyue Kan; Nana Song; Qiuyu Pang; Huan Mei; Hailin Zheng; Dongmei Li; Fan Cui; Guixia Lv; Ruifang An; Ping Li; Zhengai Xiong; Shangrong Fan; et al. (Mycopathologia, 2023)

The impact of hazes on schizophrenia admissions and the synergistic effect with the combined atmospheric oxidation capacity in Hefei, China - Jiajun Yuan; Weiwei Chang; Zhenhai Yao; Liying Wen; Jintao Liu; Rubing Pan; Weizhuo Yi; Jian Song; Shuangshuang Yan; Xuanxuan Li; Li Liu; Ning Wei; et al. (Environmental Research, 2023)

Revisiting the centrality definition and observable centrality dependence of relativistic heavy-ion collisions in PACIAE model - Yu-Liang Yan; Dai-Mei Zhou; An-Ke Lei; Xiao-Mei Li; Xiao-Ming Zhang; Liang Zheng; Gang Chen; Xu Cai; Ben-Hao Sa (Computer Physics Communications, 2023)

BnaC01.BIN2, a GSK3-like kinase, modulates plant height and yield potential in Brassica napus - Bao Li; Xinhong Liu; Yiming Guo; Lichao Deng; Liang Qu; Mingli Yan; Mei Li; Tonghua Wang (Theoretical and Applied Genetics, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

P2X7Rs: new therapeutic targets for osteoporosis - Haoyun Huang; Yu-Mei He; Miao-Miao Lin; Yanchao Wang; Xiaomei Zhang; Li Liang; Xueling He (Purinergic Signalling, 2023)
Increasing evidence suggests that both the occurrence and progression of osteoporosis are associated with inflammation, especially in primary osteoporosis. The maintenance of skeletal homeostasis is dependent on the complex regulation of bone metabolism. Numerous evidence suggested that purinoceptor networks are essential for bone homeostasis. In this review, the relationship between inflammation and the development of osteoporosis and the role of P2X7 receptor (P2X7R) in regulating the dynamic regulation of bone reconstruction were covered. We also discussed how P2X7R regulates the balance between resorption and bone formation by osteoblasts and reviewed the relevance of P2X7R polymorphisms in skeletal physiology. Finally, we analyzed potential targets of P2X7R for osteoporosis.

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Sex difference on fibroblast growth factors (FGFs) expression in skin and wound of streptozotocin(STZ)-induced type 1 diabetic mice - Nuo-qi Wang; Wei-hua Jia; Lin Yin; Na Li; Mei-dai Liang; Jia-min Shang; Bi-yu Hou; Li Zhang; Gui-fen Qiang; Guan-hua Du; Xiu-ying Yang (Molecular Biology Reports, 2023)

Mental health, health-related quality of life, and lung function after hospital discharge in healthcare workers with severe COVID-19: a cohort study from China - Lijuan Xiong; Qian Li; Xiongjing Cao; Huangguo Xiong; Daquan Meng; Mei Zhou; Yanzhao Zhang; Xinliang He; Yupeng Zhang; Liang Tang; Yang Jin; Jiahong Xia; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Distribution and physical–biological controls of dimethylsulfide in the western tropical Indian Ocean during winter monsoon - Shi-Mei Liang; Xing Zhai; Cheng-Xuan Li; Ming Xin; Ping Sun; Xuan-Li Liu; Lin Liu; Bao-Dong Wang (Frontiers in Marine Science, 2023)
New field observation on distribution, turnover, and sea–air flux of three dimethylated sulfur compounds (dimethylsulfide (DMS), dimethylsulfoniopropionate, and dimethylsulfoxide) in the western tropical Indian Ocean (WTIO; 4°N–10°S, 61°–65°E) were conducted under the major Global Change and Air–Sea Interaction Program during the 2021/2022 Northeast Monsoon (December 21, 2021 to January 11, 2022). Significantly high surface concentrations of DMS were identified in the region of the Seychelles–Chagos Thermocline Ridge (SCTR; 5°–10°S). This occurred because the shallow thermocline/nitracline and associated upwelling fueled biological production of DMS in the subsurface, which was brought to the surface through vertical mixing. The calculated sea–air DMS flux was also significantly strong in the SCTR region during the Northeast Monsoon owing to combination of high wind speed and high surface concentration of DMS. This finding is similar to results obtained previously during the Southwest Monsoon, suggesting that the SCTR region is an area of active DMS emission during both the Northeast Monsoon and the Southwest Monsoon. Microbial consumption was the dominant pathway of DMS removal, accounting for 74.4% of the total, whereas the processes of photolysis (17.7%) and ventilation (7.9%) were less important. Future work should be undertaken in the WTIO to establish how DMS emission is linked to aerosol properties and climate change.

Divergent responses in the gut microbiome and liver metabolome to ammonia stress in three freshwater turtles - Qin-Yuan Meng; Dong-Mei Mo; Han Li; Wan-Ling Wang; Hong-Liang Lu (Science of The Total Environment, 2023)

The increased medical burden associated with frailty is partly attributable to household solid fuel: A nationwide prospective study of middle-aged and older people in China - Xiaoyu Jin; Yuling Wang; Yudong Wu; Yunfeng Liang; Yuxuan Li; Xiaoni Sun; Shuangshuang Yan; Lu Mei; Junwen Tao; Jian Song; Rubing Pan; Weizhuo Yi; et al. (Science of The Total Environment, 2023)

Hydrogen-bond induced enhanced emission ratiometric fluorescent handy needle for visualization assay of amoxicillin by smartphone sensing platform - Lingfei Li; Liang Yang; Dan Lin; Shihao Xu; Chunsheng Mei; Shaoming Yu; Changlong Jiang (Journal of Hazardous Materials, 2023)

Estimating the CO2 emissions of Chinese cities from 2011 to 2020 based on SPNN-GNNWR - Lizhi Miao; Sheng Tang; Xinting Li; Dingyu Yu; Yamei Deng; Tian Hang; Haozhou Yang; Yunxuan Liang; Mei-Po Kwan; Lei Huang (Environmental Research, 2023)

Improving the regional deployment of carbon mitigation efforts by incorporating air-quality co-benefits: A multi-provincial analysis of China - Hong-Dian Jiang; Pallav Purohit; Qiao-Mei Liang; Li-Jing Liu; Yu-Fei Zhang (Ecological Economics, 2023)

3D-printed SiC lattices integrated with lightweight quartz fiber/silica aerogel sandwich structure for thermal protection system - Hui Mei; Hao Li; Zhipeng Jin; Liangjun Li; Dou Yang; Chengyu Liang; Laifei Cheng; Litong Zhang (Chemical Engineering Journal, 2023)

A rotating paper-based microfluidic sensor array combining Michael acceptors and carbon quantum dots for discrimination of biothiols - Liang Zhu; Xuecui Mei; Zhengchun Peng; Jiang Liu; Jiao Yang; Yingchun Li (Chemical Engineering Journal, 2023)

In situ phytostabilization of arable soils severely contaminated with cadmium at Yangshuo, Southern China, using cash crops and amendments: a comprehensive performance evaluation - Bo-Fang Yan; Mei-Lin Yan; Xue Xiao; Rong-Liang Qiu; Yuan-Qing Chao; Yin-Xin Li; Su-Lian Lv; Zhong-Xin Tan; Ye-Tao Tang (Journal of Soils and Sediments, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

Phenotypic aging mediates the association between blood cadmium and depression: a population-based study - Yudong Wu; Qing Wu; Rubing Pan; Weizhuo Yi; Yuxuan Li; Xiaoyu Jin; Yunfeng Liang; Lu Mei; Shuangshuang Yan; Xiaoni Sun; Wei Qin; Jian Song; et al. (Environmental Science and Pollution Research, 2023)

Human CYP1B1 enzyme-mediated, AhR enhanced activation of aflatoxin B1 for its genotoxicity in human cells - Yuting Chen; Zhaohong Lu; Boxin Li; Huanhuan Wang; Tikeng Jiang; Mei Xuan; Hui Yang; Jialong Chen; Xiaoshan Liu; Hairong Liang; Yungang Liu; Huanwen Tang (Toxicology Letters, 2023)

Effects of urban particulate matter on gut microbiome and partial schizophrenia-like symptoms in mice: Evidence from shotgun metagenomic and metabolomic profiling - Weizhuo Yi; Yifu Ji; Hua Gao; Shengyong Luo; Rubing Pan; Jian Song; Yangyang He; Yuxuan Li; Yudong Wu; Shuangshuang Yan; Yunfeng Liang; Xiaoni Sun; et al. (Science of The Total Environment, 2023)

Short-term exposure to air pollution is an emerging but neglected risk factor for schizophrenia: A systematic review and meta-analysis - Rong Song; Li Liu; Ning Wei; Xuanxuan Li; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Lu Mei; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Regional convergence analysis of sustainable innovation efficiency in European Union countries - Kai Xu; Ran Mei; Li Liang; Wei Sun (Journal of Environmental Management, 2023)

Lattice doping of Zn boosts oxygen vacancies in Co3O4 Nanocages: Improving persulfate activation via forming Surface-Activated complex - Mei-Mei Wang; Li-Juan Liu; Jia-Rui Xi; Ying Ding; Peng-Xi Liu; Liang Mao; Bing-Jie Ni; Wei-Kang Wang; Juan Xu (Chemical Engineering Journal, 2023)

Transforming growth factor-β signaling: From tissue fibrosis to therapeutic opportunities - Li-Li Ren; Xiao-Jun Li; Ting-Ting Duan; Zheng-Hai Li; Jun-Zheng Yang; Ya-Mei Zhang; Liang Zou; Hua Miao; Ying-Yong Zhao (Chemico-Biological Interactions, 2023)

Removal of Cd from contaminated farmland soil by washing with residues of traditional Chinese herbal medicine extracts - Yi Wang; Yuan Li; Shuai Yang; Qi-hao Wang; Shao-cheng Si; Han-yi Mei; Guo-ming Liu; Xiang-liang Pan; Yong-ming Luo (Environmental Science and Pollution Research, 2022)

Rootstock rescues watermelon from Fusarium wilt disease by shaping protective root-associated microbiomes and metabolites in continuous cropping soils - An-Hui Ge; Zhi-Huai Liang; Li-Li Han; Ji-Ling Xiao; Yi Zhang; Qing Zeng; Ji-Fang Xiang; Chao Xiong; Li-Mei Zhang (Plant and Soil, 2022)

Is higher ambient temperature associated with acute appendicitis hospitalizations? A case-crossover study in Tongling, China - Yuxuan Li; Xuelian Luo; Yudong Wu; Shuangshuang Yan; Yunfeng Liang; Xiaoyu Jin; Xiaoni Sun; Lu Mei; Chao Tang; Xiangguo Liu; Yangyang He; Weizhuo Yi; et al. (International Journal of Biometeorology, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Relationship of night sleep duration with health lifestyle, depressive symptoms, internet addiction in Chinese High school Students - Yueyang Hu; Tingting Gao; Ruilin Cao; Hui Ren; Zeying Qin; Chuanen Li; Leilei Liang; Cuicui Meng; Xinmeng Guo; Jianping Lv; Songli Mei (Sleep and Biological Rhythms, 2022)

Ectomycorrhizal synthesis between two Tuber species and six tree species: are different host-fungus combinations having dissimilar impacts on host plant growth? - Lan-Lan Huang; Yan-Liang Wang; Alexis Guerin-Laguette; Ran Wang; Peng Zhang; Yong-Mei Li; Fu-Qiang Yu (Mycorrhiza, 2022)

Ambra1 regulates apoptosis and chemosensitivity in breast cancer cells through the Akt-FoxO1-Bim pathway - Wei-liang Sun; Ling-yan He; Li Liang; Si-yu Liu; Jie Luo; Mei-ling Lv; Zheng-wen Cai (Apoptosis, 2022)

Increase in rosmarinic acid accumulation and transcriptional responses of synthetic genes in hairy root cultures of Prunella vulgaris induced by methyl jasmonate - Mei Ru; Yonghua Li; Min Guo; Liuyan Chen; Yong Tan; Liang Peng; Zongsuo Liang (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Fine mapping of qDB.A03, a QTL for rapeseed branching, and identification of the candidate gene - Bao Li; Tonghua Wang; Yiming Guo; Xinhong Liu; Lichao Deng; Liang Qu; Mei Li (Molecular Genetics and Genomics, 2022)

Identification of epigenetic modifications mediating the antagonistic effect of selenium against cadmium-induced breast carcinogenesis - Zhuo-Zhi Liang; Yi-Xin Zhang; Rui-Mei Zhu; Yue-Lin Li; Hong-Mei Jiang; Ruo-Bi Li; Qian-Xin Chen; Qing Wang; Lu-Ying Tang; Ze-Fang Ren (Environmental Science and Pollution Research, 2022)

Effects of extreme precipitation on hospitalization risk and disease burden of schizophrenia in urban and rural Lu’an, China, from 2010 to 2019 - Yudong Wu; Zhenghai Yao; Gongyan Ma; Jian Cheng; Huabin Xu; Wei Qin; Weizhuo Yi; Rubing Pan; Qiannan Wei; Chao Tang; Xiangguo Liu; Yangyang He; et al. (Environmental Science and Pollution Research, 2022)

Effect of feed restriction on the intestinal microbial community structure of growing ducks - Jun-peng Li; Qi-fan Wu; Sheng-chao Ma; Jian-mei Wang; Bin Wei; Yang Xi; Chun-chun Han; Liang Li; Hua He; He-he Liu (Archives of Microbiology, 2022)

Antimicrobial Natural Products Produced by Soil-Derived Fungus Penicillium cremeogriseum W1-1 - Xu-Yan Sang; Zhao-Jie Wang; Ya-Bin Yang; Yong-Liang Wang; Mei-Ling Xiang; Dou-Ying Zhu; Ying Zhou; Xiao-Dong Luo; Li-Xing Zhao (Indian Journal of Microbiology, 2021)

Characterization and identification of SFDC ‐1, a novel AmpC ‐type β‐lactamase in Serratia fonticola - Xu Dong; Peiyao Zhang; Kexin Zhou; Jialei Liang; Qiaoling Li; Xueya Zhang; Danying Zhou; Wei Lu; Zhewei Sun; Hongmao Liu; Junwan Lu; Xi Lin; et al. (Environmental Microbiology, 2021)
Summary The clinical and environmental infections caused by AmpC β‐lactamases have been increasingly reported recently. In this study, we characterize the novel chromosome‐encoded AmpC β‐lactamase SFDC‐1 identified in Serratia fonticola strain R28, which was isolated from a rabbit raised on a farm in southern China. SFDC‐1 shared the highest amino acid identity of 79.6% with the functionally characterized AmpC β‐lactamase gene bla YRC‐1 , although it had highly homologous functionally uncharacterized relatives in the same species from different sources, including some of the clinical significance. The cloned bla SFDC‐1 exhibited resistance to a broad spectrum of β‐lactam antibiotics, including most cephalosporins with the highest resistance to ampicillin, cefazolin and ceftazidime, with increased MIC levels ≥128‐fold compared with the control strains. The purified SFDC‐1 showed catalytic activities against β‐lactams with the highest catalytic activity to cefazolin. The genetic context of bla SFDC‐1 and its relatives was conserved in the chromosome, and no mobile genetic elements were found surrounding them.

Antibiotic Resistance Characterization of Bacteria Isolated from Traditional Chinese Paocai - Mei Li; Yao Tang; Liyan Guo; Tao Lei; Yunfei Deng; Liang Wang; Qisheng Zhang; Chengkang Li (Current Microbiology, 2021)

Genetic and molecular characterization of determinant of six-rowed spike of barley carrying vrs1.a4 - Jin-Hui Wang; Zhen-Mei Xu; Xue-Bing Qiu; Li-Lan Li; Shui-Yang Yu; Tao Li; Yan-Yan Tang; Xi Pu; Juan-Yu Zhang; Hai-Li Zhang; Jun-Jun Liang; Ya-Wei Tang; et al. (Theoretical and Applied Genetics, 2021)

Interaction of magnolia bark extracts with Staphylococcus aureus DNA and evaluation of the stability of their antibacterial activities - Shu-Mei Cui; Hai-yun Liang; Ting Li; Ke-Ke He; Yu-Mei Zheng; Meng Tang; Chong-rong Ke; Li-Ya Song (Archives of Microbiology, 2021)

Cysestermerol A, a rare stilbene sestermer with significant hypoglycemic activities from Cynodon dactylon - Feng Wang; Li Zhang; Bi-Jun Li; Qiu-Ming Liang; A-Li Chen; Zhen-Feng Fang; Shu-Mei Wang (Natural Product Research, 2021)

Electricity end-use and construction activity are key leverage points for co-controlling greenhouse gases and local pollution in China - Li-Jing Liu; Qiao-Mei Liang; Felix Creutzig; Nan Cheng; Lan-Cui Liu (Climatic Change, 2021)

Inhibition of the p38 MAPK pathway attenuates renal injury in pregnant rats with acute necrotizing pancreatitis - Jiacheng Zhang; Fangchao Mei; Liang Zhao; Teng Zuo; Yupu Hong; Man Li; Jia Yu; Weixing Wang (Immunologic Research, 2021)

Spatial prediction of soil calcium carbonate content based on Bayesian maximum entropy using environmental variables - Mei Shan; Shuang Liang; Hongchen Fu; Xiaoli Li; Yu Teng; Jingwen Zhao; Yaxin Liu; Chen Cui; Li Chen; Hai Yu; Shunbang Yu; Yanling Sun; et al. (Nutrient Cycling in Agroecosystems, 2021)

Isolation and Identification of Pseudomonas sp. Strain DY-1 from Agricultural Soil and Its Degradation Effect on Prometryne - Dong Liang; Ming-yue Ding; Chang-yixin Xiao; Ya-wen Shen; Yin-yue Wang; Hai-tao Li; Rong-mei Liu; Ji-guo Gao (Current Microbiology, 2021)

Puerhibacterium puerhi gen. nov., sp. nov., a novel member of the family Promicromonosporaceae, isolated from Pu-erh tea pile-fermentation - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Lu Han; Wen-Shu Peng; Li Liu; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

Paenibacillus puerhi sp. nov., isolated from the rhizosphere soil of Pu-erh tea plants (Camellia sinensis var. assamica) - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Xing-Hua Wang; Wen-Jie Zhang; Li Zhuang; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Honokiol induces paraptosis-like cell death of acute promyelocytic leukemia via mTOR & MAPK signaling pathways activation - Xiaoli Liu; Yan Gu; Yaoyao Bian; Danhong Cai; Yu Li; Ye Zhao; Zhaofeng Zhang; Mei Xue; Liang Zhang (Apoptosis, 2021)
Acute promyelocytic leukemia (APL) is a blood system disease caused by the accumulation of a large number of immature blood cells in bone marrow. Although the introduction of all- trans retinoic acid (ATRA) and arsenic has reached a high level of complete remission rate and 5-year disease-free survival rate, the occurrence of various adverse reactions still severely affects the quality of life of patients. As a natural product, honokiol (HNK) has the advantages of low toxicity and high efficiency, and it is a potential drug for the treatment of cancer. Since cancer cells can escape apoptotic cell death through multiple adaptive mechanisms, HNK, a drug that induces cancer cell death in a nonapoptotic way, has attracted much interest. We found that HNK reduced the viability of human APL cell line (NB4 cells) by inducing paraptosis-like cell death. The process was accompanied by excessive reactive oxygen species (ROS), mitochondrial damage, endoplasmic reticulum stress, and increased microtubule-associated protein 1 light chain 3 (LC3) processing. The inactivation of proteasome activity was the main cause of misfolded and unfolded protein accumulation in endoplasmic reticulum, such as LC3II/I and p62. This phenomenon could be alleviated by adding cycloheximide (CHX), a protein synthesis inhibitor. We found that mTOR signaling pathway participated in paraptosis-like cell death induced by HNK in an autophagy-independent process. Moreover, the mitogen-activated protein kinase (MAPK) signaling pathway induced paraptosis of NB4 cells by promoting endoplasmic reticulum stress. In summary, these findings indicate that paraptosis may be a new way to treat APL, and provide novel insights into the potential mechanism of paraptosis-like cell death.

Essential oil from Artemisia annua aerial parts: composition and repellent activity against two storage pests - Hong Liu; Shan-Shan Guo; Li Lu; Dian Li; Jun Liang; Zhong-Hui Huang; Yan-Mei Zhou; Wen-Juan Zhang; Shushan Du (Natural Product Research, 2021)

Effectiveness of predicting spatial contaminant distributions at industrial sites using partitioned interpolation method - Pengwei Qiao; Sucai Yang; Wenxia Wei; Peizhong Li; Yanjun Cheng; Shuang Liang; Mei Lei; Tongbin Chen (Environmental Geochemistry and Health, 2021)

Design of a downlink algorithm for rotary steering (logging while drilling) systems - Liang Yao; Wang Mei-Shan; Liu Peng; Zhu Bo; Ma Li; Sun Yan (Applied Geophysics, 2020)

Spororrminone A and 2- epi -spororrminone A, two new chromones from an endolichenic fungus Sporormiella irregularis - Mei-Juan Huang; Yan-Jun Li; Jia Tang; Guo-Dong Chen; Dan Hu; Wei Xu; Liang-Dong Guo; Xin-Sheng Yao; Hao Gao (Natural Product Research, 2020)

Aluminum and magnesium status during pregnancy and placenta oxidative stress and inflammatory mRNA expression: China Ma’anshan birth cohort study - Jian-Qing Wang; Ya-Bin Hu; Chun-Mei Liang; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Yan Li; Peng Zhu; Jia-Hu Hao; et al. (Environmental Geochemistry and Health, 2020)

Erratum to: Herbal decoctosome is a novel form of medicine - Xiaoyun Li; Zhu Liang; Jianchao Du; Zhiqing Wang; Song Mei; Zhiqing Li; Yan Zhao; Dandan Zhao; Yiming Ma; Jun Ye; Jiantao Xu; Yu Zhao; et al. (Science China Life Sciences, 2020)

Comparing GWAS and Brain Structure-Specific Gene Expression Profiles Identifies Psychiatric Disorder-Related Brain Structures at Different Developmental Stages - Xin Qi; Cuiyan Wu; Yanan Du; Shiqiang Cheng; Yan Wen; Mei Ma; Chujun Liang; Li Liu; Bolun Cheng; Lu Zhang; Ping Li; Feng Zhang (Neuroscience Bulletin, 2020)

Pseudomonas Saliphila sp. nov., a Bacterium Isolated from Oil-Well Production Water in Qinghai Oilfield of China - Xiao-Juan Zhang; Hong-Can Liu; Yu-Guang Zhou; Xiao-Lei Wu; Yong Nie; Qi-Rui Li; Mei-Zhu Wang; Liang Zhao; Man Cai; Ying-Qian Kang (Current Microbiology, 2020)

The association between dioxins and steroid hormones in general adult males: a cross-sectional study in an e-waste region of China - Li Li Shi; Mei Qin Wang; Shoji F. Nakayama; Chau-Ren Jung; Yue Hua Wang; Jing Jian Dong; Chao Chen Ma; Teruhiko Kido; Xian Liang Sun; Hao Feng (Environmental Science and Pollution Research, 2020)

Anti-hypertensive effects of Radix Rehmanniae and its active ingredients - Chiu-Haw Chao; Jue-Liang Hsu; Mu-Fen Chen; Ya-Hu Shih; Chia-Hui Lee; Mei-Li Wu; Chi-I Chang (Natural Product Research, 2020)

SNX-2112, an Hsp90 inhibitor, suppresses cervical cancer cells proliferation, migration, and invasion by inhibiting the Akt/mTOR signaling pathway - Liang-Shun Fu; Hong-Hong Qiu; Min Liu; Liu-Bing Hu; Yan Wang; Peng-Chao Zhang; Man-Mei Li; Yi-Fei Wang; Zhong Liu (Medicinal Chemistry Research, 2020)

Sugar transporter genes in grass carp (Ctenopharyngodon idellus): molecular cloning, characterization, and expression in response to different stocking densities - Xiao Liang; Fengying Yan; Yu Gao; Mei Xiong; Haishan Wang; Kommaly Onxayvieng; Rong Tang; Li Li; Xi Zhang; Wei Chi; Marina Piria; Mirna Mrkonjić Fuka; et al. (Fish Physiology and Biochemistry, 2020)

Antibacterial Effects of Schisandra chinensis Extract on Escherichia coli and its Applications in Cosmetic - S. Mei Cui; T. Li; Q. Wang; K. Ke He; Y. Mei Zheng; H. Yun Liang; L. Ya Song (Current Microbiology, 2020)

Naturally Occurring Antibodies to Tau Exists in Human Blood and Are Not Changed in Alzheimer’s Disease - Zhong-Yuan Yu; Wei-Wei Li; Hai-Mei Yang; Noralyn B. Mañucat-Tan; Jun Wang; Ye-Ran Wang; Bin-Lu Sun; Zi-Cheng Hu; Li-Li Zhang; Liang Tan; Juan Deng; Yu-Hui Liu (Neurotoxicity Research, 2020)

Aluminum-induced “mixed” cell death in mice cerebral tissue and potential intervention - Yan-xia Hao; Mei-qin Li; Jing-si Zhang; Qin-li Zhang; Xia Jiao; Xiu-liang Ji; Huan Li; Qiao Niu (Neurotoxicity Research, 2020)

Myelin Deficits Caused by Olig2 Deficiency Lead to Cognitive Dysfunction and Increase Vulnerability to Social Withdrawal in Adult Mice - Xianjun Chen; Fei Wang; Jingli Gan; Zhonghua Zhang; Xuejun Liang; Tao Li; Nanxin Huang; Xiaofeng Zhao; Feng Mei; Lan Xiao (Neuroscience Bulletin, 2020)

Evaluating the Genetic Correlations Between Left-Handedness and Mental Disorder Using Linkage Disequilibrium Score Regression and Transcriptome-Wide Association Study - Bolun Cheng; Chujun Liang; Ping Li; Li Liu; Shiqiang Cheng; Mei Ma; Lu Zhang; Xin Qi; Yan Wen; Feng Zhang (Biochemical Genetics, 2020)

The inhibition of miR-17-5p promotes cortical neuron neurite growth via STAT3/GAP-43 pathway - Liang Zhang; Zhijie Wang; Bo Li; Ziwei Xia; Xin Wang; Yucai Xiu; Zheng Zhang; Chuanjie Chen; Hong Song; Wenhua Li; Mei Yu; Meiling Zhang; et al. (Molecular Biology Reports, 2020)

Characterization of a jointed rock mass based on fractal geometry theory - Lichen Li; Wenbing Wu; M. Hesham El Naggar; Guoxiong Mei; Rongzhu Liang (Bulletin of Engineering Geology and the Environment, 2019)

Stress-dependent anisotropy index of strength and deformability of jointed rock mass: insights from a numerical study - Na Wu; Zheng-zhao Liang; Ying-chun Li; Hong Li; Wan-run Li; Mei-li Zhang (Bulletin of Engineering Geology and the Environment, 2019)

Degradation of 3-fluoroanilne by Rhizobium sp. JF-3 - Zhi-Qing Zhao; Tu-Cai Zheng; Wen-Jing Zhang; Xiao-Li Shen; Liang Lv; Yan-Mei Li (Biodegradation, 2019)

Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Song-mei Lou; Min Zhang; Zheng-rong Wu; Gui-xing Jiang; Hua Shen; Yi Dai; Yue-long Liang; Li-ping Cao; Guo-ping Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Interferon gamma inhibits transmissible gastroenteritis virus infection mediated by an IRF1 signaling pathway - Lingling Shan; Fang Fu; Mei Xue; Xiangdong Zhu; Liang Li; Li Feng; Pinghuang Liu (Archives of Virology, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

The complete chloroplast genome of Taiwania cryptomerioides (Cupressales: Cupressaceae), an endangered relict conifer species endemic to East Asia - Ling-Li Wang; Yong-Liang Shi; Qi-Lin Zhang; Yan-Ru Guo; Hong-Mei Teng (Conservation Genetics Resources, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Effects of perinatal dioxin exposure on development of children: a 3-year follow-up study of China cohort - Zheng Wang; Jin Guo Hang; Hao Feng; Li Li Shi; Jing Jian Dong; Bin Shen; Ting Luo; Ren Mei Cai; Ling Jie Shen; Teruhiko Kido; Xian Liang Sun (Environmental Science and Pollution Research, 2019)

Successful Treatment of Eczema-Like Mucormycosis in a Child by Combination of Intravenous Drip and Percutaneous Injection Amphotericin B - Mei-hua Fu; Jia Liu; Guan-zhao Liang; Cheng-rang Li; Xiao-mei Zhu; Le Wang; Hao Chen; Wen-long Hu; Gui-xia Lv; Wei-da Liu (Mycopathologia, 2019)

Herbal decoctosome is a novel form of medicine - Xiaoyun Li; Zhu Liang; Jianchao Du; Zhiqing Wang; Song Mei; Zhiqing Li; Yan Zhao; Dandan Zhao; Yiming Ma; Jun Ye; Jiantao Xu; Yu Zhao; et al. (Science China Life Sciences, 2019)

SB203580 attenuates acute lung injury and inflammation in rats with acute pancreatitis in pregnancy - Yu Zhou; Hongmiao Xia; Liang Zhao; Fangchao Mei; Man Li; Yundong You; Kailiang Zhao; Weixing Wang (Inflammopharmacology, 2019)

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

Genomic and Transcriptomic Analysis Identified Gene Clusters and Candidate Genes for Oil Content in Peanut (Arachis hypogaea L.) - Xiaohua Wang; Ping Xu; Liang Yin; Yan Ren; Shuangling Li; Yanmao Shi; Thomas D. Alcock; Qing Xiong; Wei Qian; Xiaoyuan Chi; Manish K. Pandey; Rajeev K. Varshney; et al. (Plant Molecular Biology Reporter, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Identification, characterization and expression analysis of genes involved in steroidal saponin biosynthesis in Dracaena cambodiana - Jia-Hong Zhu; Hui-Liang Li; Dong Guo; Ying Wang; Hao-Fu Dai; Wen-Li Mei; Shi-Qing Peng (Journal of Plant Research, 2018)

Successful Treatment by Surgery of a Primary Cutaneous Mucormycosis Caused by Mucor irregularis - Guan-zhao Liang; Wen-qi Xu; Xiao-li Zheng; Huan Mei; Gui-xia Lv; Yong-nian Shen; Dong-mei Li; Wei-da Liu (Mycopathologia, 2018)

Use of freeze-dried bone allografts in osteoporotic patients undergoing median sternotomy - Mei Liang; Jianzhou Liu; Qi Miao; Guotao Ma; Xingrong Liu; Xiaofeng Li; Chaoji Zhang (Cell and Tissue Banking, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Barcode index numbers expedite quarantine inspections and aid the interception of nonindigenous mealybugs (Pseudococcidae) - Jing-Mei Ren; Muhammad Ashfaq; Xu-Nan Hu; Jun Ma; Fan Liang; Paul D. N. Hebert; Li Lin; Jean François Germain; Muhammad Z. Ahmed (Biological Invasions, 2018)

Knockdown of PRMT1 suppresses IL-1β-induced cartilage degradation and inflammatory responses in human chondrocytes through Gli1-mediated Hedgehog signaling pathway - Lei Xia; Hong-Xing Zhang; Mei-Li Xing; Yu-Ben Xu; Peng Li; Liang-Ku Huang; Jie Bai; Zhao Tian; Zan-Dong Zhao (Molecular and Cellular Biochemistry, 2018)

Complementary feeding patterns among ethnic groups in rural western China - Peng-fei Qu; Ya Zhang; Jia-mei Li; Ruo Zhang; Jiao-mei Yang; Fang-liang Lei; Shan-shan Li; Dan-meng Liu; Shao-nong Dang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2018)

Involvement of IL-17 in Secondary Brain Injury After a Traumatic Brain Injury in Rats - Tan Li; Yong-mei Zhang; Dong Han; Rong Hua; Bing-nan Guo; Shu-qun Hu; Xian-liang Yan; Tie Xu (NeuroMolecular Medicine, 2017)

Cloning and characterization of Agp1, the gene encoding the small subunit of ADP-glucose pyrophosphorylase from wheat and its relatives - Xiao-Wei Zhang; Qing Wang; Ling-Ling Zhang; Xiao-Juan Zhong; Qian-Tao Jiang; Jian Ma; Peng-Fei Qi; Wei Li; Guo-Yue Chen; Xiu-Jin Lan; Mei Deng; Zhen-Xiang Lu; et al. (Biologia, 2017)

Molecular identification of differential expression genes associated with sex pheromone biosynthesis in Spodoptera exigua - Ya-Nan Zhang; Long-Wa Zhang; Da-Song Chen; Liang Sun; Zhao-Qun Li; Zhan-Feng Ye; Mei-Yan Zheng; Jin-Bu Li; Xiu-Yun Zhu (Molecular Genetics and Genomics, 2017)

Modulatory role of L-carnitine against microcystin-LR-induced immunotoxicity and oxidative stress in common carp - Xiu-Mei Chen; Gui-Liang Guo; Li Sun; Qiu-Shi Yang; Gui-Qin Wang; Dong-Ming Zhang (Fish Physiology and Biochemistry, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Effects of Excess Copper Ions on Decidualization of Human Endometrial Stromal Cells - Ying Li; Zhen-Long Kang; Na Qiao; Lian-Mei Hu; Yong-Jiang Ma; Xiao-Huan Liang; Ji-Long Liu; Zeng-Ming Yang (Biological Trace Element Research, 2017)

Molecular cloning and characterisation of two enzymes involved in the rosmarinic acid biosynthesis pathway of Prunella vulgaris L. - Mei Ru; Kunru Wang; Zhenqing Bai; Liang Peng; Shaoxuan He; Tianlin Pei; Yanyan Jia; Hongyan Li; Zongsuo Liang (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Erratum to: Molecular characteristics of the ompA gene of serotype B Chlamydia trachomatis in Qinghai Tibetan primary school students - Xue Li; Shaoya Zhang; Qingfeng Liang; Mei Wang; Ailian Hu; Xiuyuan Li; Benshan Yang; Mingxin Zhang; Ningli Wang; Xinxin Lu (Science China Life Sciences, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

High seroprevalence of toxoplasma gondii and HIV-1 co-infection among drug users in Yunnan province, southwest China - Xin Chen; Mei Ye; Yan-Heng Zhou; Feng-Liang Liu; Lin Duo; Hong Li; Wei Pang; Yong-Tang Zheng (Science China Life Sciences, 2016)

Molecular characteristics of the ompA gene of serotype B Chlamydia trachomatis in Qinghai Tibetan primary school students - Xue Li; Shaoya Zhang; Qingfeng Liang; Mei Wang; Ailian Hu; Xiuyuan Li; Benshan Yang; Mingxin Zhang; Ningli Wang; Xinxin Lu (Science China Life Sciences, 2016)

LncRNA NONRATT021972 siRNA attenuates P2X7 receptor expression and inflammatory cytokine production induced by combined high glucose and free fatty acids in PC12 cells - Hong Xu; Luling He; Changle Liu; Lan Tang; Yonghu Xu; Mengqi Xiong; Mei Yang; Yongfang Fan; Fangfang Hu; Xingzi Liu; Lu Ding; Yun Gao; et al. (Purinergic Signalling, 2016)

The proteome and phosphoproteome of maize pollen uncovers fertility candidate proteins - Qing Chao; Zhi-fang Gao; Yue-feng Wang; Zhe Li; Xia-he Huang; Ying-chun Wang; Ying-chang Mei; Biligen-gaowa Zhao; Liang Li; Yu-bo Jiang; Bai-chen Wang (Plant Molecular Biology, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Comparison of the virulence and cognate virulence factors of multinucleate, binucleate and uninucleate Rhizoctonia isolates, causing sheath blight on maize plants - Shanyue Zhou; Ying Liu; Mei Zhang; Baodu Li; Xujun Chen; Wenxing Liang (European Journal of Plant Pathology, 2016)

Context- and time-dependent neurobiological and behavioral sensitization induced by a single morphine exposure in mice - Wang-Jun Qin; Yan-Ting Wang; Peng-Mei Li; Xiao-Xing Wang; Jun-Xu Li; Hamid R. Noori; Rick E. Bernardi; Jian-Hui Liang; Xiang-Lin Zhang (Psychopharmacology, 2016)

Cyanobacteria in the complex river-connected Poyang Lake: horizontal distribution and transport - Xia Liu; Yun-Liang Li; Bao-Gui Liu; Kui-Mei Qian; Yu-Wei Chen; Jun-Feng Gao (Hydrobiologia, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

A global spectral element model for poisson equations and advective flow over a sphere - Huan Mei; Faming Wang; Zhong Zeng; Zhouhua Qiu; Linmao Yin; Liang Li (Advances in Atmospheric Sciences, 2016)

The meso-mechanism study of gypsum rock weakening in brine solutions - Wei Dong Yu; Wei Guo Liang; Yan Rong Li; Yan Mei Yu (Bulletin of Engineering Geology and the Environment, 2016)

Chemotherapeutic agent CPT-11 eliminates peritoneal resident macrophages by inducing apoptosis - Mei-Yun Huang; Hao Pan; Yi-Dan Liang; Hong-Xia Wei; Li-Hui Xu; Qing-Bing Zha; Xian-Hui He; Dong-Yun Ouyang (Apoptosis, 2016)

Establishment of Salvia castanea Diels f. tomentosa Stib. hairy root cultures and the promotion of tanshinone accumulation and gene expression with Ag+, methyl jasmonate, and yeast extract elicitation - Bo Li; Bangqing Wang; Hongyan Li; Liang Peng; Mei Ru; Zongsuo Liang; Xijun Yan; Yonghong Zhu (Protoplasma, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

Dissimilarity of phytoplankton assemblages in two connected tropical reservoirs: effects of water transportation and environmental filtering - Li-Juan Xiao; Ren Hu; Liang Peng; La-Mei Lei; Yu Feng; Bo-Ping Han (Hydrobiologia, 2016)

Genetic diversity and phylogenetic relationships of citron (Citrus medica L.) and its relatives in southwest China - Xiaoming Yang; Hang Li; Mei Liang; Qiang Xu; Lijun Chai; Xiuxin Deng (Tree Genetics & Genomes, 2015)

Rice grassy stunt virus nonstructural protein p5 serves as a viral suppressor of RNA silencing and interacts with nonstructural protein p3 - Chao Zhang; Xiao-juan Liu; Kang-cheng Wu; Lu-Ping Zheng; Zuo-mei Ding; Fei Li; Peng Zou; Liang Yang; Jian-guo Wu; Zu-jian Wu (Archives of Virology, 2015)

Pectin Modifications: A Review - Jun Chen; Wei Liu; Cheng-Mei Liu; Ti Li; Rui-Hong Liang; Shun-Jing Luo (Critical Reviews in Food Science and Nutrition, 2015)

Transcriptome analysis reveals the potential contribution of long noncoding RNAs to brown adipocyte differentiation - Liang hui You; Li jun Zhu; Lei Yang; Chun mei Shi; Ling xia Pang; Jun Zhang; Xian wei Cui; Chen bo Ji; Xi rong Guo (Molecular Genetics and Genomics, 2015)

A uninucleate Rhizoctonia sp. from maize plant with ITS heterogeneity and hypersensitive to abiotic stresses - Shanyue Zhou; Mei Zhang; Ying Liu; Ji Zhen; Wenxing Liang; Xujun Chen; Zejian Guo; Baodu Li (European Journal of Plant Pathology, 2015)

Ectopic expression of a phytochrome B gene from Chinese cabbage (Brassica rapa L. ssp. pekinensis) in Arabidopsis thaliana promotes seedling de-etiolation, dwarfing in mature plants, and delayed flowering - Mei-Fang Song; Shu Zhang; Pei Hou; Hong-Zhong Shang; Hai-Ke Gu; Jing-Juan Li; Yang Xiao; Lin Guo; Liang Su; Jian-Wei Gao; Jian-Ping Yang (Plant Molecular Biology, 2015)

Inhibition of isoflavone biosynthesis enhanced T-DNA delivery in soybean by improving plant–Agrobacterium tumefaciens interaction - Yan-Min Zhang; Hong-Mei Zhang; Zi-Hui Liu; Xiu-Lin Guo; Hui-Cong Li; Guo-Liang Li; Chun-Zhi Jiang; Meng-Chen Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

The wheat NHX antiporter gene TaNHX2 confers salt tolerance in transgenic alfalfa by increasing the retention capacity of intracellular potassium - Yan-Min Zhang; Hong-Mei Zhang; Zi-Hui Liu; Hui-Cong Li; Xiu-Lin Guo; Guo-Liang Li (Plant Molecular Biology, 2015)

Determination of royal jelly freshness by ELISA with a highly specific anti-apalbumin 1, major royal jelly protein 1 antibody - Li-rong Shen; Yi-ran Wang; Liang Zhai; Wen-xiu Zhou; Liang-liang Tan; Mei-lu Li; Dan-dan Liu; Fa Xiao (Journal of Zhejiang University-SCIENCE B, 2015)

Genome-wide discovery of novel and conserved microRNAs in white shrimp (Litopenaeus vannamei) - Qian-Yun Xi; Yuan-Yan Xiong; Yuan-Mei Wang; Xiao Cheng; Qi-En Qi; Gang Shu; Song-Bo Wang; Li-Na Wang; Ping Gao; Xiao-Tong Zhu; Qing-Yan Jiang; Yong-Liang Zhang; et al. (Molecular Biology Reports, 2015)

TGFβ can stimulate the p38/β-catenin/PPARγ signaling pathway to promote the EMT, invasion and migration of non-small cell lung cancer (H460 cells) - Li-Chiung Lin; Shih-Lan Hsu; Chieh-Liang Wu; Chi-Mei Hsueh (Clinical & Experimental Metastasis, 2014)

Identification of a novel SHOX mutation in a Chinese family with isolated Madelung deformity - LIBIN MEI; YANRU HUANG; QIAN PAN; HAOXIAN LI; DESHENG LIANG; LINGQIAN WU (Journal of Genetics, 2014)

Isolation and characterization of twenty-five polymorphic microsatellite markers in Siniperca scherzeri Steindachner and cross-species amplification - WEI HUANG; XU-FANG LIANG; CHUN-MEI QU; JI LI; LIANG CAO (Journal of Genetics, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Shinjulactone O, a new quassinoid from the root bark of Ailanthus altissima - Xiao-Lin Yang; Yong-Liang Yuan; Dong-Mei Zhang; Fei Li; Wen-Cai Ye (Natural Product Research, 2014)

Clinical Factors Associated With the Diagnosis and Progression of Diabetic Nephropathy - Shuang Liang; Qian Li; Han-Yu Zhu; Jian-Hui Zhou; Rui Ding; Xiang-Mei Chen; Guang-Yan Cai (Cell Biochemistry and Biophysics, 2014)

The checkpoint 1 kinase inhibitor LY2603618 induces cell cycle arrest, DNA damage response and autophagy in cancer cells - Feng-Ze Wang; Hong-rong Fei; Ying-Jie Cui; Ying-Kun Sun; Zhao-Mei Li; Xue-Ying Wang; Xiao-Yi Yang; Ji-Guo Zhang; Bao-Liang Sun (Apoptosis, 2014)

Trehalose Metabolism-Related Genes in Maize - Mei-Liang Zhou; Qian Zhang; Zhan-Min Sun; Li-Hui Chen; Bo-Xin Liu; Kai-Xuan Zhang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Journal of Plant Growth Regulation, 2014)

Intergeneric hybrids between Chrysanthemum morifolium ‘Nannongxiaoli’ and Artemisia vulgaris ‘Variegata’ show enhanced resistance against both aphids and Alternaria leaf spot - Wen-ying Zhu; Fei Zhang; Su-mei Chen; Li-li Xu; Liang Wang; Hai-bin Wang; Xiang-yu Qi; Hui-yun Li; Fadi Chen (Euphytica, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

National vulnerability to extreme climatic events: the cases of electricity disruption in China and Japan - Jing-Li Fan; Qiao-Mei Liang; Xiao-Jie Liang; Hirokazu Tatano; Yoshio Kajitani; Yi-Ming Wei (Natural Hazards, 2014)

Geochronology and geochemistry of the Late Triassic Longtan pluton in South China: termination of the crustal melting and Indosinian orogenesis - Liang Qiu; Dan-Ping Yan; Mei-Fu Zhou; Nicholas T. Arndt; Shuang-Li Tang; Liang Qi (International Journal of Earth Sciences, 2014)

Further studies on Toxascaris leonina (Linstow, 1902) (Ascaridida: Ascarididae) from Felis lynx (Linnaeus) and Panthera leo (Linnaeus) (Carnivora: Felidae) - Li-Mei Xue; Jing-Bo Chai; Yan-Ning Guo; Lu-Ping Zhang; Liang Li (Acta Parasitologica, 2014)
Toxascaris leonina (Linstow, 1902) is a most common intestinal parasite of various animals in Felidae and Canidae. In the present paper, light and scanning electron microscopy (SEM) were used to study the morphological aspects of adult worms of this nematode in detail, based on the material collected from Panthera leo (Linnaeus) and Felis lynx (Linnaeus) (Carnivora: Felidae) in China. The results showed that there were some morphometric differences between the present material and the previous studies, including the body size, the width and length of cervical alae, the number of denticles on each lip and the tail length of the female. Previously unreported morphological features were also revealed. These supplementary morphological and morphometric data contributed to a more accurate identification of this worldwide distributed ascarid nematode.

Potassium (K) effects and QTL mapping for K efficiency traits at seedling and adult stages in wheat - Fan-Mei Kong; Ying Guo; Xue Liang; Chun-Hong Wu; Ying-Ying Wang; Yan Zhao; Si-Shen Li (Plant and Soil, 2013)

Remifentanil preconditioning alleviating brain damage of cerebral ischemia reperfusion rats by regulating the JNK signal pathway and TNF-α/TNFR1 signal pathway - Yan Zhang; Yan-Wei Li; Ya-Xin Wang; Hong-Tao Zhang; Xiao-Mei Zhang; Yu Liang; Xiu-Shan Zhang; Wen-Sheng Wang; Hai-Gen Liu; Yi Zhang; Ling Zhang; Yu-Hua Zheng (Molecular Biology Reports, 2013)

Uptake of arsenic species by turnip ( Brassica rapa L.) and lettuce ( Lactuca sativa L.) treated with roxarsone and its metabolites in chicken manure - Lian Xi Huang; Li Xian Yao; Zhao Huan He; Chang Min Zhou; Guo Liang Li; Bao Mei Yang; Ying Fen Li (Food Additives & Contaminants: Part A, 2013)

Sweet Preference Modified by Early Experience in Mice and the Related Molecular Modulations on the Peripheral Pathway - Wei-Li Li; Meng-Ling Chen; Si-Si Liu; Guo-Liang Li; Tian-Yuan Gu; Pei Liang; Yu-Mei Qin; Yue-Hua Zhan; Ying Quan; Gen-Hua Zhang (Journal of Molecular Neuroscience, 2013)

Novel triterpenoid saponins from the seeds of Celosia argentea L. - Qing Bin Wu; Yan Wang; Lin Liang; Qian Jiang; Mei Li Guo; Jun Jie Zhang (Natural Product Research, 2013)

HIF-1α up-regulates NDRG1 expression through binding to NDRG1 promoter, leading to proliferation of lung cancer A549 cells - Qiang Wang; Li-Hong Li; Guo-Dong Gao; Gang Wang; Liang Qu; Jin-Ge Li; Chun-Mei Wang (Molecular Biology Reports, 2013)

Intergeneric hybrid between Chrysanthemum × morifolium and Artemisia japonica achieved via embryo rescue shows salt tolerance - Wen-ying Zhu; Jia-fu Jiang; Su-mei Chen; Liang Wang; Li-li Xu; Hai-bin Wang; Pei-ling Li; Zhi-yong Guan; Fa-di Chen (Euphytica, 2013)

Identification of genetic associations of SP110/MYBBP1A/RELA with pulmonary tuberculosis in the Chinese Han population - Lei Cai; Shao-Li Deng; Li Liang; Hui Pan; Jia Zhou; Mei-Yan Wang; Jun Yue; Chun-Ling Wan; Guang He; Lin He (Human Genetics, 2013)

Interactive effects of morphine and dopaminergic compounds on spatial working memory in rhesus monkeys - Jian-Hong Wang; Joshua Dominie Rizak; Yan-Mei Chen; Liang Li; Xin-Tian Hu; Yuan-Ye Ma (Neuroscience Bulletin, 2013)

Hydro-mechanical experiments on suffusion under long-term large hydraulic heads - Yu-long Luo; Liang Qiao; Xing-xing Liu; Mei-li Zhan; Jin-chang Sheng (Natural Hazards, 2013)

Late Paleoproterozoic sedimentary rock-hosted stratiform copper deposits in South China: their possible link to the supercontinent cycle - Xin-Fu Zhao; Mei-Fu Zhou; Jian-Wei Li; Liang Qi (Mineralium Deposita, 2013)

Biomass accumulation and partitioning, photosynthesis, and photosynthetic induction in field-grown maize (Zea mays L.) under low- and high-nitrogen conditions - Jun-Wen Chen; Zhi-Qing Yang; Ping Zhou; Mei-Rong Hai; Tian-Xiang Tang; Yan-Li Liang; Tong-Xin An (Acta Physiologiae Plantarum, 2013)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

QTL mapping for seedling traits in wheat grown under varying concentrations of N, P and K nutrients - Ying Guo; Fan-mei Kong; Yun-feng Xu; Yan Zhao; Xue Liang; Ying-ying Wang; Diao-guo An; Si-shen Li (Theoretical and Applied Genetics, 2012)

MicroRNA- 1 represses Cx43 expression in viral myocarditis - Hong-Fei Xu; Yu-Jie Ding; Yi-Wen Shen; Ai-Min Xue; Hong-Mei Xu; Cheng-Liang Luo; Bei-Xu Li; Yue-Lin Liu; Zi-Qin Zhao (Molecular and Cellular Biochemistry, 2012)

Catalytic characteristics of plant-esterase from wheat flour - Chang-jun Hou; Kun He; Li-min Yang; Dan-qun Huo; Mei Yang; Shun Huang; Liang Zhang; Cai-hong Shen (World Journal of Microbiology and Biotechnology, 2012)

Identification and expression analysis of four 14-3-3 genes during fruit ripening in banana (Musa acuminata L. AAA group, cv. Brazilian) - Mei-Ying Li; Bi-Yu Xu; Ju-Hua Liu; Xiao-Liang Yang; Jian-Bin Zhang; Cai-Hong Jia; Li-Cheng Ren; Zhi-Qiang Jin (Plant Cell Reports, 2012)

Simultaneous determination of aerosol optical thickness and surface reflectance using ASTER visible to near-infrared data over land - Jie Guang; Yong Xue; Ying Wang; Yingjie Li; Linlu Mei; Hui Xu; Shunlin Liang; Jindi Wang; Linyan Bai (International Journal of Remote Sensing, 2011)

Purification and anticancer activity investigation of pentacyclic triterpenoids from the leaves of Sinojackia sarcocarpa L.Q. Luo by high-speed counter-current chromatography - Sujun Liu; Mei Cao; Daxu Li; Jie Zhang; Su Feng; Yuanyang Nie; Liang Yan; Dan Zhang; Yan Zhang; Zhirong Yang; Jian Zhao (Natural Product Research, 2011)

Involvement of OsNPR1/NH1 in rice basal resistance to blast fungus Magnaporthe oryzae - Jia-Xun Feng; Lin Cao; Juan Li; Cheng-Jie Duan; Xue-Mei Luo; Ning Le; Haihong Wei; Shujia Liang; Chengcai Chu; Qinghua Pan; Ji-Liang Tang (European Journal of Plant Pathology, 2011)

Effective Gene Delivery to Mesenchymal Stem Cells Based on the Reverse Transfection and Three-Dimensional Cell Culture System - Cai-Xia He; Ni Li; Yu-Lan Hu; Xiu-Mei Zhu; Hai-Jie Li; Min Han; Pei-Hong Miao; Zhong-Jie Hu; Gang Wang; Wen-Quan Liang; Yasuhiko Tabata; Jian-Qing Gao (Pharmaceutical Research, 2011)

QTL mapping of sheath blight resistance in a deep-water rice cultivar - Dong Fu; Liang Chen; Guohui Yu; Yi Liu; Qiaojun Lou; Hanwei Mei; Liang Xiong; Mingshou Li; Xiaoyan Xu; Lijun Luo (Euphytica, 2011)

Two new compounds from Semen celosiae and their protective effects against CCl 4 -induced hepatotoxicity - Qian Xue; Zhen-Liang Sun; Mei-Li Guo; Ying Wang; Ge Zhang; Xiao-Kang Wang (Natural Product Research, 2011)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

Enhancement of salt tolerance in alfalfa transformed with the gene encoding for betaine aldehyde dehydrogenase - Zi-Hui Liu; Hong-Mei Zhang; Guo-Liang Li; Xiu-Lin Guo; Shou-Yi Chen; Gui-Bo Liu; Yan-Min Zhang (Euphytica, 2011)

Determination of optimal carbon source and pH value for sclerotial formation of Polyporus umbellatus under artificial conditions - Yong-Mei Xing; Juan Chen; Ya-Li Lv; Han-Qiao Liang; Shun-Xing Guo (Mycological Progress, 2011)

Isolation of a LEAFY homolog from Populus tomentosa: expression of PtLFY in P. tomentosa floral buds and PtLFY-IR-mediated gene silencing in tobacco (Nicotiana tabacum) - Xin-Min An; Dong-Mei Wang; Ze-Liang Wang; Bo Li; Wen-Hao Bo; Guan-Lin Cao; Zhi-Yi Zhang (Plant Cell Reports, 2011)

A multiple-dose pharmacokinetics of polyethylene glycol recombinant human interleukin-6 (PEG-rhIL-6) in rats - Xue-ling He; Hai-lin Yin; Jiang Wu; Ke Zhang; Yan Liu; Tao Yuan; Hai-lin Rao; Liang Li; Guang Yang; Xue-mei Zhang (Journal of Zhejiang University-SCIENCE B, 2011)

Population genetic analysis of 15 autosomal STR loci in the Russian population of northeastern Inner-Mongolia, China - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shuan-liang Fan; Li-bin Deng; Feng Chen; Li-ping Chen; Hong-dan Wang; Zhen-yuan Wang; Rudolf Lucas; Zhen-min Lian (Molecular Biology Reports, 2010)

Altered Expression of the Small Guanosine Triphosphatase RhoA in Human Temporal Lobe Epilepsy - Jie Yuan; Lin-yuan Wang; Jin-mei Li; Ning-jia Cao; Liang Wang; Gui-bo Feng; Tao Xue; Yang Lu; Xue-feng Wang (Journal of Molecular Neuroscience, 2010)

A fibrillar form of fibronectin induces apoptosis by activating SHP-2 and stress fiber formation - Chun-Yung Huang; Chi-Ming Liang; Chiao-Li Chu; Jei-Ming Peng; Shu-Mei Liang (Apoptosis, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Synthesis and evaluation of antiinflammatory activity of substituted chalcone derivatives - Xue-Wu Zhang; Dong-Hai Zhao; Ying-Chun Quan; Liang-Peng Sun; Xiu-Mei Yin; Li-Ping Guan (Medicinal Chemistry Research, 2010)

Expression of a bee venom phospholipase A2 from Apis cerana cerana in the baculovirus-insect cell - Li-rong Shen; Mei-hui Ding; Li-wen Zhang; Wei-guang Zhang; Liang Liu; Duo Li (Journal of Zhejiang University-SCIENCE B, 2010)

Fluorescent Property of the Gd3+-Doped Terbium Complexes and Crystal Structure of [Tb(TPTZ)(H2O)6]Cl3·3H2O - Yan-Fang Zhao; Yong-Liang Zhao; Feng Bai; Xiao-yan Wei; Yong-sheng Zhou; Mei-na Shan; Huan-huan Li; Rui-jun Ma; Xiao-tao Fu; Yan Du (Journal of Fluorescence, 2010)

Treatment strategies for Parkinson’s disease - Hong Yuan; Zhen-Wen Zhang; Li-Wu Liang; Quan Shen; Xiang-Dang Wang; Su-Mei Ren; Hong-Jie Ma; Shu-Jun Jiao; Ping Liu (Neuroscience Bulletin, 2010)

Distributions of HLA-A and -B alleles and haplotypes in the Yi ethnic minority of Yunnan, China: relationship to other populations - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shun-zhi Liu; Ya-jun Deng; Shuan-liang Fan; Li-bin Deng; Feng Chen; Ping Zhang; Jie Fang; Li-ping Chen; et al. (Journal of Zhejiang University-SCIENCE B, 2010)

A single-nucleotide polymorphism of the TNFAIP3 gene is associated with systemic lupus erythematosus in Chinese Han population - Li-Qiong Cai; Zai-Xing Wang; Wen-Sheng Lu; Jian-Wen Han; Liang-Dan Sun; Wen-Hui Du; Shu-Mei Zhang; Xian-Bo Zuo; Xue-Jun Zhang; Sen Yang (Molecular Biology Reports, 2010)

DAZL binds to 3′UTR of Tex19.1 mRNAs and regulates Tex19.1 expression - Mei Zeng; Yilu Lu; Xiaolin Liao; Dan Li; Huaqin Sun; Suhua Liang; Sizhong Zhang; Yongxin Ma; Zhirong Yang (Molecular Biology Reports, 2009)

Selection of housekeeping genes for gene expression studies on the development of fruit bearing shoots in Chinese jujube (Ziziphus jujube Mill.) - Hai-feng Sun; Yu-ping Meng; Gui-mei Cui; Qiu-fen Cao; Jie Li; Ai-hua Liang (Molecular Biology Reports, 2009)

Isolation and characterization of microsatellite markers for Primulina tabacum, a critically endangered perennial herb - Zheng-Feng Wang; Hai Ren; Qian-Mei Zhang; Wan-Hui Ye; Kai-Ming Liang; Zhong-Chao Li (Conservation Genetics, 2009)

Infection and replication of avian influenza H5N1 virus in an infected human - Jing-Jiao Zhou; Dan-Yun Fang; Jie Fu; Jiang Tian; Jun-Mei Zhou; Hui-Jun Yan; Yu Liang; Li-Fang Jiang (Virus Genes, 2009)

Effects of Neuregulin on Expression of MMP-9 and NSE in Brain of Ischemia/Reperfusion Rat - Qin Li; Rui Zhang; Yin-lin Ge; Yuan-wu Mei; Yun-liang Guo (Journal of Molecular Neuroscience, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

The Avoidance Responses of Daphnia magna to the Exposure of Organophosphorus Pesticides in an On-Line Biomonitoring System - Zong-Ming Ren; Zhi-Liang Li; Jin-Miao Zha; Kai-feng Rao; Mei Ma; Zijian Wang; Rong-Shu Fu (Environmental Modeling & Assessment, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Effect of Neuregulin on Apoptosis and Expressions of STAT3 and GFAP in Rats Following Cerebral Ischemic Reperfusion - Qin Li; Rui Zhang; Yun-liang Guo; Yuan-wu Mei (Journal of Molecular Neuroscience, 2009)

Purification of recombinant laccase from Trametes versicolor in Pichia methanolica and its use for the decolorization of anthraquinone dye - Mei Guo; Fuping Lu; Minyao Liu; Tuoping Li; Jun Pu; Na Wang; Peng Liang; Chenyun Zhang (Biotechnology Letters, 2008)

Controls on variations of platinum-group element concentrations in the sulfide ores of the Jinchuan Ni-Cu deposit, western China - Shangguo Su; Chusi Li; Mei-Fu Zhou; Edward M. Ripley; Liang Qi (Mineralium Deposita, 2008)

A major QTL associated with cold tolerance at seedling stage in rice (Oryza sativa L.) - Qiaojun Lou; Liang Chen; Zongxiu Sun; Yongzhong Xing; Jun Li; Xiaoyan Xu; Hanwei Mei; Lijun Luo (Euphytica, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Effects of moderate and severe intermittent hypoxia on vascular endothelial function and haemodynamic control in sedentary men - Jong-Shyan Wang; Liang-Yu Chen; Li-Lan Fu; Mei-Ling Chen; May-Kuen Wong (European Journal of Applied Physiology, 2007)

Expressions of polypeptide: N-acetylgalactosaminyltransferase in leukemia cell lines during 1,25-dihydroxyvitamin D3 induced differentiation - Hao Qiu; Xiang-Hong Guo; Jian-Hua Mo; Mei-Fang Jin; Shi-Liang Wu; Hui-Li Chen (Glycoconjugate Journal, 2006)

Soil microbial biomass as affected by non-flooded plastic mulching cultivation in rice - Yong-Shan Li; Liang-Huan Wu; Xing-Hua Lu; Li-Mei Zhao; Qiao-Lan Fan; Fu-Suo Zhang (Biology and Fertility of Soils, 2006)

Secreted Expression and Purification of Dengue 2 Virus Full-length Nonstructural Glycoprotein NS1 in Pichia. pastoris - Jun-mei Zhou; Yun-xia Tang; Dan-yun Fang; Jing-jiao Zhou; Yu Liang; Hui-yu Guo; Li-fang Jiang (Virus Genes, 2006)

Molecular Cloning and Expression of IL2 cDNA from the Tibet Pig - Li Hui; Gao Rong; Wu Mei; Wang Li-Huan; Fu Man-Liang; Wu Kai-Yuan (Veterinary Research Communications, 2005)

Crystal structure studies on rubrerythrin: enzymatic activity in relation to the zinc movement - Mei Li; Ming-yih Liu; Jean LeGall; Lu-lu Gui; Jun Liao; Tao Jiang; Ji-ping Zhang; Dong-cai Liang; Wen-rui Chang (JBIC Journal of Biological Inorganic Chemistry, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)